Composition for functional layer of electrochemical element, laminate for electrochemical element, and electrochemical element
By using a combination of specific granular polymers and bonding materials, the electrochemical element functional layer is formed, and the problem of insufficient wet adhesion in the prior art is solved, and higher adhesion and cyclic characteristics are achieved.
Patent Information
- Application Number
- CN202411716149.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-31
- Filing Date
- 2023-03-06
- Publication Date
- 2025-03-11
AI Technical Summary
There is room for improvement in the wet adhesion of the existing electrochemical component functional layer after the electrolyte is impregnated.
A particulate polymer containing a specific volume of particle size D50 and a particle size distribution α is used as the composition for the functional layer of the electrochemical element, and an appropriate bonding material, non-conductive heat-resistant particles and amine compounds are combined to form an excellent wet adhesive functional layer.
The wet and dry adhesion of electrochemical components is significantly improved, and the adhesion resistance of the functional layer and the cycling characteristics of the electrochemical components are enhanced.
Smart Images

Figure SMS_1 
Figure SMS_3
Abstract
Description
[0001] This application is a divisional application of the invention patent application with application number 202380012062.1. The application date of the original application is March 6, 2023, and the name of the invention is "Composition for electrochemical element functional layer, laminate for electrochemical element, and electrochemical element". Technical Field
[0002] The present invention relates to a composition for an electrochemical device functional layer, a laminate for an electrochemical device, and an electrochemical device. Background Art
[0003] Electrochemical devices such as lithium-ion secondary batteries and electric double layer capacitors are used in a wide range of applications because they are small, lightweight, have high energy density, and can be repeatedly charged and discharged.
[0004] Here, for example, a lithium ion secondary battery generally includes a positive electrode, a negative electrode, and battery components such as a separator that separates the positive electrode from the negative electrode to prevent a short circuit between the positive electrode and the negative electrode.
[0005] In an electrochemical element such as a lithium ion secondary battery, a constituent element having a functional layer such as an adhesive layer for the purpose of improving the adhesion between constituent elements is used. Specifically, an electrode formed by further forming a functional layer on an electrode substrate and a separator formed by forming a functional layer on a separator substrate are used as battery components, and the above-mentioned electrode substrate is formed by arranging an electrode composite material layer on a current collector. In addition, in recent years, further improvements in the functional layer are being studied for the purpose of further improving the performance of electrochemical elements such as lithium ion secondary batteries. Specifically, for example, in Patent Document 1, it is proposed that a granular polymer having an average roundness of 0.90 or more and less than 0.99 and a volume average particle size of 1.0 μm or more and 10.0 μm or less is added to a composition for an electrochemical element functional layer to form a functional layer capable of exerting excellent adhesion.
[0006] Prior art literature Patent Literature Patent document 1: International Publication No. 2020 / 175292. Summary of the invention
[0007] Problem that the invention aims to solve However, there is room for further improvement in the adhesiveness of the functional layer formed using the above-mentioned conventionally known particulate polymer or the like after immersion in an electrolyte solution (hereinafter also referred to as "wet adhesiveness").
[0008] Therefore, an object of the present invention is to provide a composition for an electrochemical element functional layer, which can form a functional layer having excellent wet adhesiveness.
[0009] Another object of the present invention is to provide an electrochemical device laminate having a functional layer formed using the electrochemical device functional layer composition, and an electrochemical device having the electrochemical device laminate.
[0010] Solutions for solving problems The present inventors have conducted in-depth research to achieve the above-mentioned purpose. Then, the present inventors newly discovered that if the composition for the electrochemical element functional layer contains a granular polymer having a specified volume particle size D50 and a specified particle size distribution (hereinafter sometimes referred to as "particle size distribution α"), the above-mentioned problem can be solved, thereby completing the present invention.
[0011] That is, the purpose of the present invention is to advantageously solve the above-mentioned problems. The present invention is a composition for an electrochemical element functional layer, which contains a granular polymer, the granular polymer has a volume particle size D50 of 1.0 μm or more and 10.0 μm or less, and the granular polymer has a particle size distribution α, and the particle size distribution α is that when the granular polymer is taken as 100% by volume, the proportion of particles having a particle size of 1.5 times or more of the volume particle size D50 is 0.5% by volume or more and 5.0% by volume or less. If it is such a composition for an electrochemical element functional layer, a functional layer with excellent wet adhesion can be formed.
[0012] In this specification, the volume particle size D50 of the particulate polymer refers to the particle size at which the cumulative volume calculated from the small particle size side in the particle size distribution (volume basis) measured using a particle size distribution analyzer is 50%, and can be measured by the method described in the Examples.
[0013] In the composition for the functional layer of an electrochemical element of the present invention, the above-mentioned granular polymer preferably has an average roundness of greater than 0.95 and less than 0.99, and the above-mentioned granular polymer has the following roundness distribution, wherein the above-mentioned roundness distribution is that the proportion of particles having a roundness less than 0.95 is less than 10% relative to the above-mentioned granular polymer on a number basis.
[0014] If the average circularity of the particulate polymer is greater than the above lower limit, in the functional layer formed using the electrochemical element functional layer composition, the number of bonding points between the particulate polymer and materials other than the particulate polymer increases, and the components constituting the functional layer are prevented from falling off (so-called powdering), resulting in improved wet adhesion. In addition, the adhesion before electrolyte immersion (hereinafter also referred to as "dry adhesion") can also be improved.
[0015] On the other hand, when the average circularity of the particulate polymer is not more than the upper limit, the state of the particulate polymer in the functional layer is stabilized and powdering can be suppressed, resulting in improved wet adhesiveness and dry adhesiveness.
[0016] If the proportion of particles having a roundness of less than 0.95 in the particulate polymer is less than the upper limit, the number of bonding points between the particulate polymer and materials other than the particulate polymer increases in the functional layer, and powdering can be suppressed, resulting in improved wet adhesiveness and dry adhesiveness.
[0017] In the present specification, the average circularity and circularity distribution of the particulate polymer can be measured by the method described in Examples of the present specification.
[0018] In the composition for an electrochemical device functional layer of the present invention, it is preferred that the amount of the particulate polymer dissolved in tetrahydrofuran (hereinafter also referred to as “THF”) is 5% by mass or more and 50% by mass or less.
[0019] When the amount of the particulate polymer dissolved in tetrahydrofuran is not less than the above lower limit, the particulate polymer is appropriately deformed at the contact surface between the functional layer formed using the electrochemical device functional layer composition and the electrochemical device member in contact, resulting in improved wet adhesion and dry adhesion.
[0020] On the other hand, if the dissolution amount of the granular polymer in tetrahydrofuran is below the above upper limit, the excessive deformation of the granular polymer is suppressed, and as a result, the adhesion (so-called adhesion) of the functional layer to the electrochemical element component can be suppressed when, for example, a laminate or electrochemical element having a functional layer is wound and stored and transported. That is, the adhesion resistance of the functional layer can be improved. In addition, in the electrochemical element, the dissolution amount of the component of the granular polymer that can cause the resistance value to rise in the electrolyte is reduced, and as a result, the cycle characteristics of the electrochemical element can be improved.
[0021] In the present specification, “the amount of the particulate polymer dissolved in tetrahydrofuran” can be measured by the method described in Examples of the present specification.
[0022] In the composition for the functional layer of an electrochemical element of the present invention, it is preferred that the granular polymer is formed by particles comprising a polymer, wherein the polymer contains an aromatic monovinyl monomer unit and at least one cross-linking monomer unit selected from an aromatic divinyl monomer unit, a di(meth)acrylate monomer unit, a tri(meth)acrylate monomer unit, and an ethylenically unsaturated monomer unit containing an epoxy group, and the content ratio of the cross-linking monomer unit is greater than 0.1% by mass and less than 5% by mass when all repeating units in the polymer are taken as 100% by mass.
[0023] If the particulate polymer is formed from particles comprising a polymer containing an aromatic monovinyl monomer unit, wet adhesiveness and dry adhesiveness can be improved.
[0024] If the granular polymer is formed of particles containing a polymer, and the polymer contains the cross-linkable monomer unit, wet adhesion can be improved. In addition, excessive deformation of the granular polymer is suppressed, and as a result, the anti-blocking property of the functional layer can be improved. Furthermore, in the electrochemical element, the amount of dissolution of the granular polymer component that can cause the resistance value to increase in the electrolyte is reduced, and as a result, the cycle characteristics of the electrochemical element can be improved.
[0025] When the content ratio of the cross-linkable monomer unit is not less than the above lower limit, the blocking resistance of the functional layer and the cycle characteristics of the electrochemical device can be improved.
[0026] On the other hand, when the content ratio of the crosslinkable monomer unit is not more than the above upper limit, the particulate polymer is appropriately deformed, and as a result, the wet adhesiveness and the dry adhesiveness can be improved.
[0027] In this specification, a polymer "contains a monomer unit" means "a polymer obtained using the monomer contains a structural unit derived from the monomer." In addition, the content ratio of the monomer unit in the polymer can be expressed as 1 The determination was carried out by nuclear magnetic resonance (NMR) methods such as H-NMR.
[0028] In the present specification, "(meth)acrylic acid" means acrylic acid and / or methacrylic acid.
[0029] In the electrochemical device functional layer composition of the present invention, the content ratio of the polymerization initiator decomposition product in the particles constituting the particulate polymer is preferably 20 ppm or less based on the total mass of the particles constituting the particulate polymer.
[0030] If the content of the polymerization initiator decomposition products in the particles is below the upper limit, the anti-blocking property of the functional layer can be improved. In addition, in the electrochemical element, the amount of polymerization initiator decomposition products eluted into the electrolyte solution that can cause the resistance value to increase is reduced, and as a result, the cycle characteristics can be improved.
[0031] In the present specification, the "content ratio of the polymerization initiator decomposition product" can be measured using chromatography. Specifically, for example, it can be measured using the method described in Examples of the present specification.
[0032] The composition for an electrochemical device functional layer of the present invention preferably further contains a binder.
[0033] If the electrochemical element functional layer composition further contains a binder, powdering can be suppressed and wet adhesiveness and dry adhesiveness can be improved.
[0034] In the composition for an electrochemical device functional layer of the present invention, it is preferred that the binder material contains a (meth)acrylic acid ester monomer unit and an acid group-containing monomer unit.
[0035] If the adhesive material contains a (meth)acrylate monomer unit and an acid group-containing monomer unit, wet adhesiveness and dry adhesiveness can be further improved.
[0036] The composition for an electrochemical device functional layer of the present invention preferably further contains an amine compound.
[0037] When the electrochemical element functional layer composition further contains an amine compound, corruption of the electrochemical element functional layer composition can be suppressed, thereby improving the storage stability of the electrochemical element functional layer composition.
[0038] The composition for an electrochemical device functional layer of the present invention preferably further contains non-conductive heat-resistant particles.
[0039] If the electrochemical element functional layer composition further contains non-conductive heat-resistant particles, the heat resistance of the functional layer can be improved.
[0040] In addition, the object of the present invention is to advantageously solve the above-mentioned problem. The present invention is a laminate for an electrochemical element, which has a substrate and a functional layer formed on the substrate, and the functional layer is formed using the electrochemical element functional layer composition. If it is such a laminate for an electrochemical element, the cycle characteristics of the electrochemical element having the laminate for an electrochemical element can be improved.
[0041] Another object of the present invention is to advantageously solve the above-mentioned problems, and the present invention is an electrochemical device having the above-mentioned electrochemical device laminate. Such an electrochemical device can exhibit excellent cycle characteristics.
[0042] Effects of the Invention According to the present invention, there can be provided a composition for an electrochemical element functional layer capable of forming a functional layer having excellent wet adhesiveness.
[0043] Furthermore, according to the present invention, there can be provided an electrochemical device laminate having a functional layer formed using the electrochemical device functional layer composition and an electrochemical device having the electrochemical device laminate. DETAILED DESCRIPTION
[0044] Hereinafter, embodiments of the present invention will be described in detail.
[0045] Here, the electrochemical element functional layer composition of the present invention (hereinafter also referred to as "functional layer composition") can be used as a material for forming a functional layer possessed by the electrochemical element laminate of the present invention (hereinafter also referred to as "laminate"). In addition, the electrochemical element laminate of the present invention can be used to manufacture the electrochemical element of the present invention.
[0046] (Composition for electrochemical element functional layer) The electrochemical element functional layer composition of the present invention contains a predetermined particulate polymer and can optionally contain a binder, non-conductive heat-resistant particles, an amine compound, and other components. Such a functional layer composition can form a functional layer having excellent wet adhesiveness.
[0047] The composition for a functional layer of the present invention is usually a slurry composition in which a particulate polymer is dispersed in water as a dispersion medium.
[0048] <Particle-like polymer> The granular polymer contained in the composition for functional layer is a polymer having a predetermined volume particle diameter D50 and a predetermined particle size distribution α, and having a granular shape in the composition for functional layer, as described in detail below. In addition, after the components are bonded to each other via the functional layer formed using the composition for functional layer, the granular polymer may be granular or in any other shape. Furthermore, the granular polymer may be a crystalline polymer, a non-crystalline polymer, or a mixture thereof.
[0049] <<Volume particle size D50 of granular polymer>> The particulate polymer has a volume particle diameter D50 of 1.0 μm or more and 10.0 μm or less.
[0050] If the volume particle size D50 of the granular polymer is above the above lower limit, the granular polymer protrudes relative to the material other than the granular polymer on the thickness direction surface of the functional layer formed using the functional layer composition and becomes easy to contact the electrochemical element components, resulting in the functional layer being able to exhibit excellent wet adhesion and dry adhesion.
[0051] On the other hand, if the volume particle size D50 of the granular polymer is below the above upper limit, in the functional layer formed using the functional layer composition, the number of bonding points between the granular polymer and materials other than the granular polymer increases, thereby suppressing powder loss, resulting in the functional layer being able to exhibit excellent wet adhesion and dry adhesion.
[0052] The volume particle size D50 of the particulate polymer is preferably 2.0 μm or more, more preferably 2.3 μm or more, and even more preferably 2.5 μm or more, and is preferably 9.0 μm or less, more preferably 7.0 μm or less, and even more preferably 6.0 μm or less.
[0053] The volume particle size D50 of the particulate polymer can be adjusted by the type and amount of the metal hydroxide used in preparing the particulate polymer and the method and conditions for preparing the particulate polymer. The metal hydroxide will be described in detail later.
[0054] <<Particle size distribution α of granular polymer>> The particulate polymer has a particle size distribution α, wherein the proportion of particles having a particle size 1.5 times or more of the volume particle size D50 (hereinafter also referred to as “large particles”) is 0.5% to 5.0% by volume when the particulate polymer is taken as 100% by volume.
[0055] If the proportion of large particles of the granular polymer is greater than the above lower limit, the functional layer can exhibit excellent wet adhesion and dry adhesion. The reason is not clear, but it is speculated that when the functional layer and the electrode member are bonded, the large particles appropriately enter the tiny irregularities existing on the surface of the electrode member.
[0056] On the other hand, if the proportion of large particles of the granular polymer is below the above upper limit, the functional layer can exhibit excellent wet adhesion and dry adhesion. The reason is not clear, but it is speculated that when the functional layer and the electrode member are bonded, the contact between the particles having a particle size less than 1.5 times the volume particle size D50 (hereinafter also referred to as "small particles") and the electrode member is not hindered by the large particles and can be well maintained.
[0057] The proportion of large particles of the particulate polymer is preferably 1.0% by volume or more, more preferably 1.5% by volume or more, and is preferably 4.5% by volume or less, more preferably 4.0% by volume or less.
[0058] The ratio of large particles of the particulate polymer can be adjusted by the type and amount of the metal hydroxide used in preparing the particulate polymer and the method and conditions for preparing the particulate polymer.
[0059] The particulate polymer preferably has a particle size distribution α in which the proportion of particles having a particle size 3.0 times or more of the volume particle size D50 (hereinafter also referred to as “coarse particles”) is 2.0% by volume or less when the particulate polymer is taken as 100% by volume.
[0060] When the ratio of the coarse particles of the particulate polymer is not more than the above upper limit, the small particles in the functional layer sufficiently contribute to the adhesion with the electrode member, and as a result, the wet adhesiveness and the dry adhesiveness can be improved.
[0061] The proportion of the coarse particles of the particulate polymer is more preferably 1.8% by volume or less, further preferably 1.5% by volume or less, and still further preferably 1.0% by volume or less.
[0062] On the other hand, the ratio of the coarse particles of the particulate polymer is, for example, 0.15% by volume or more, and may be 0.45% by volume or more.
[0063] The ratio of the coarse particles of the particulate polymer can be adjusted by the type and amount of the metal hydroxide used in preparing the particulate polymer and the method and conditions for preparing the particulate polymer.
[0064] <<Average circularity of granular polymer>> The particulate polymer preferably has an average circularity of 0.950 or more, more preferably an average circularity of 0.960 or more, preferably an average circularity of 0.995 or less, more preferably an average circularity of 0.990 or less.
[0065] When the average circularity of the particulate polymer is not less than the above lower limit, the number of bonding points between the particulate polymer and materials other than the particulate polymer increases in the functional layer formed using the functional layer composition, thereby suppressing powder loss, and as a result, improving wet adhesiveness and dry adhesiveness.
[0066] On the other hand, when the average circularity of the particulate polymer is equal to or less than the upper limit, the state of the particulate polymer in the functional layer is stabilized and powdering is suppressed, resulting in improved wet adhesiveness and dry adhesiveness.
[0067] In addition, the average circularity of the particulate polymer can be adjusted according to the preparation method and preparation conditions of the particulate polymer.
[0068] <<Circularity Distribution of Granular Polymers>> The particulate polymer preferably has a circularity distribution in which the proportion of particles having a circularity of less than 0.95 is less than 10% on a number basis relative to the particulate polymer.
[0069] If the proportion of particles having a circularity of less than 0.95 in the particulate polymer is less than the upper limit, the number of bonding points between the particulate polymer and materials other than the particulate polymer increases in the functional layer, thereby suppressing powdering, resulting in improved wet adhesiveness and dry adhesiveness.
[0070] The proportion of particles having a circularity of less than 0.95 in the particulate polymer is more preferably 8% or less, and further preferably 5% or less.
[0071] On the other hand, the proportion of particles having a circularity of less than 0.95 in the particulate polymer is, for example, 0.1% or more, may be 0.5% or more, or may be 2% or more.
[0072] In addition, the ratio of particles having a circularity of less than 0.95 in the particulate polymer can be adjusted according to the preparation method and preparation conditions of the particulate polymer.
[0073] <<Glass transition temperature of granular polymer>> The glass transition temperature (Tg) of the particulate polymer is preferably 30°C or higher, more preferably 40°C or higher, further preferably 55°C or higher, and is preferably 110°C or lower, more preferably 90°C or lower, further preferably 70°C or lower.
[0074] When the glass transition temperature of the particulate polymer is not less than the above lower limit, the blocking resistance of the functional layer can be improved.
[0075] On the other hand, when the glass transition temperature of the particulate polymer is not more than the above upper limit, even when the members are pressed and bonded to each other via the functional layer, good wet adhesiveness and dry adhesiveness of the functional layer can be obtained.
[0076] <<Dissolution amount of granular polymer in THF>> The amount of the particulate polymer dissolved in THF is preferably 5% by mass or more, more preferably 10% by mass or more, further preferably 15% by mass or more, further preferably 20% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, further preferably 30% by mass or less, further preferably 25% by mass or less.
[0077] When the amount of the particulate polymer dissolved in THF is not less than the above lower limit, the particulate polymer is appropriately deformed at the interface between the functional layer formed using the functional layer composition and another layer in contact with each other, thereby improving wet adhesiveness and dry adhesiveness.
[0078] On the other hand, if the dissolution amount of the granular polymer in THF is below the above upper limit, the excessive deformation of the granular polymer is suppressed, and as a result, the anti-blocking property of the functional layer can be improved. In addition, in the electrochemical element, the dissolution amount of the granular polymer component that can cause the resistance value to rise in the electrolyte is reduced, and as a result, the cycle characteristics of the electrochemical element can be improved.
[0079] The amount of the particulate polymer dissolved in THF can be adjusted according to the composition of the particles constituting the particulate polymer.
[0080] <<Composition of polymer contained in particles constituting granular polymer>> The polymer contained in the particles constituting the granular polymer (hereinafter also referred to as "polymer A") is not particularly limited as long as at least the volume particle size D50 of the granular polymer and the proportion of large particles are within the above-mentioned ranges, and known polymers that can be used as binders when forming a functional layer can be used.
[0081] Here, examples of the monomer unit of the polymer A include an aromatic monovinyl monomer unit, a crosslinkable monomer unit, a (meth)acrylate monomer unit, an acid group-containing monomer unit, and a fluorine atom-containing monomer unit.
[0082] The polymer A preferably contains an aromatic monovinyl monomer unit and a crosslinkable monomer unit. That is, the particulate polymer is preferably formed of particles containing the polymer A containing an aromatic monovinyl monomer unit and a crosslinkable monomer unit.
[0083] If the particulate polymer is formed of particles containing a polymer A containing an aromatic monovinyl monomer unit, wet adhesiveness and dry adhesiveness can be improved.
[0084] -Aromatic monovinyl monomer unit- Examples of the aromatic monovinyl monomer capable of forming the aromatic monovinyl monomer unit are not particularly limited, and examples thereof include styrene, α-methylstyrene, butoxystyrene, and vinylnaphthalene, among which styrene is particularly preferred.
[0085] These aromatic monovinyl monomers may be used alone or in combination of two or more at any ratio.
[0086] The content of the aromatic monovinyl monomer unit in the polymer A is preferably 30% by mass or more, more preferably 60% by mass or more, preferably 95% by mass or less, more preferably 90% by mass or less, and further preferably 85% by mass or less, when all repeating units in the polymer A are taken as 100% by mass.
[0087] When the content of the aromatic monovinyl monomer unit is not less than the above lower limit, the elasticity of the particulate polymer can be improved, the strength of the obtained functional layer can be ensured, and the adhesion between the functional layer and the substrate can be improved.
[0088] On the other hand, when the content of the aromatic monovinyl monomer unit is below the upper limit, the flexibility of the particulate polymer is improved, and the film-forming property when the functional layer composition is dried is improved, so that the adhesion between the functional layer and the substrate can be improved.
[0089] - Cross-linking monomer unit- As a monomer capable of forming a crosslinkable monomer unit, for example, a multifunctional monomer having two or more polymerizable reactive groups in the monomer can be cited. As such a multifunctional monomer, for example: allyl (meth) acrylate monomers such as allyl methacrylate; aromatic divinyl monomers such as divinylbenzene and divinylnaphthalene; di(meth) acrylate monomers such as diethylene glycol dimethacrylate, ethylene glycol dimethacrylate, diethylene glycol diacrylate, and diacrylate-1,3-butylene glycol ester; tri(meth) acrylate monomers such as trimethylolpropane trimethacrylate and trimethylolpropane triacrylate; ethylenically unsaturated monomers containing epoxy groups such as allyl glycidyl ether and glycidyl methacrylate, etc. Here, as an aromatic divinyl monomer, divinylbenzene is preferred, as a di(meth) acrylate monomer, ethylene glycol dimethacrylate is preferred, as a tri(meth) acrylate monomer, trimethylolpropane trimethacrylate is preferred, and as an ethylenically unsaturated monomer containing epoxy groups, glycidyl methacrylate is preferred.
[0090] These crosslinkable monomers may be used alone or in combination of two or more at any ratio.
[0091] Here, the crosslinkable monomer unit is preferably at least one crosslinkable monomer unit selected from the group consisting of an aromatic divinyl monomer unit, a di(meth)acrylate monomer unit, a tri(meth)acrylate monomer unit, and an ethylenically unsaturated monomer unit containing an epoxy group. That is, the granular polymer is preferably formed from particles containing a polymer A containing at least one crosslinkable monomer unit selected from the group consisting of an aromatic divinyl monomer unit, a di(meth)acrylate monomer unit, a tri(meth)acrylate monomer unit, and an ethylenically unsaturated monomer unit containing an epoxy group.
[0092] If the granular polymer is formed of particles containing polymer A, and the polymer A contains the cross-linkable monomer unit, wet adhesion can be improved. In addition, excessive deformation of the granular polymer is suppressed, and as a result, the anti-blocking property of the functional layer can be improved. Furthermore, in the electrochemical element, the amount of dissolution of the component of the granular polymer that can cause the resistance value to increase in the electrolyte is reduced, and as a result, the cycle characteristics of the electrochemical element can be improved.
[0093] Furthermore, since the blocking resistance of the functional layer and the cycle characteristics of the electrochemical element can be further improved, the crosslinking monomer unit is more preferably at least one crosslinking monomer unit selected from aromatic divinyl monomer units, di(meth)acrylate monomer units, and tri(meth)acrylate monomer units.
[0094] Furthermore, the crosslinkable monomer unit is more preferably at least one of an aromatic divinyl monomer unit and a di(meth)acrylate monomer unit because wet adhesiveness, dry adhesiveness, and swelling property of the functional layer in an electrolyte solution can be well balanced.
[0095] The content of the crosslinkable monomer unit in the polymer A is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, preferably 5% by mass or less, more preferably 2% by mass or less, and further preferably 1% by mass or less, when all repeating units in the polymer A are taken as 100% by mass.
[0096] When the content ratio of the cross-linkable monomer unit is not less than the above lower limit, the blocking resistance of the functional layer and the cycle characteristics of the electrochemical device can be improved.
[0097] On the other hand, when the content of the crosslinkable monomer unit is below the upper limit, the particulate polymer is appropriately deformed at the contact surface between the functional layer formed using the functional layer composition and the electrochemical device member in contact, resulting in improved wet adhesiveness and dry adhesiveness.
[0098] -(Meth)acrylate monomer unit- Examples of (meth)acrylate monomers that can form (meth)acrylate monomer units include butyl acrylates such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, and tert-butyl acrylate, octyl acrylates such as pentyl acrylate, hexyl acrylate, heptyl acrylate, and 2-ethylhexyl acrylate, nonyl acrylate, decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, and stearyl acrylate; and butyl methacrylates such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, and tert-butyl methacrylate, octyl methacrylates such as pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, and 2-ethylhexyl methacrylate, nonyl methacrylate, decyl methacrylate, lauryl methacrylate, n-tetradecyl methacrylate, and stearyl methacrylate. In particular, n-butyl acrylate, 2-ethylhexyl acrylate, and methyl methacrylate are preferred, and 2-ethylhexyl acrylate is more preferred.
[0099] In addition, these (meth)acrylate monomers may be used alone or in combination of two or more at any ratio.
[0100] The content ratio of the (meth)acrylic acid ester monomer unit in the polymer A is preferably 10% by mass or more, more preferably 15% by mass or more, preferably 60% by mass or less, more preferably 40% by mass or less, and further preferably 20% by mass or less, when all repeating units in the polymer A are taken as 100% by mass.
[0101] When the content ratio of the (meth)acrylic acid ester monomer units is not less than the above lower limit, an excessive decrease in the glass transition temperature of the particulate polymer can be avoided, and the blocking resistance of the obtained functional layer can be improved.
[0102] On the other hand, when the content ratio of the (meth)acrylic acid ester monomer unit is equal to or less than the above upper limit, the adhesion between the functional layer and the substrate can be made good.
[0103] In addition, in this specification, the "(meth)acrylate monomer" does not include the monomers listed as the above-mentioned "crosslinking monomer" and the monomers listed as the "acid group-containing monomer" described later.
[0104] -Acid group-containing monomer unit- Examples of the acid group-containing monomer capable of forming the acid group-containing monomer unit include a monomer having a carboxylic acid group, a monomer having a sulfonic acid group, a monomer having a phosphoric acid group, and a monomer having a hydroxyl group.
[0105] Examples of the monomer having a carboxylic acid group include monocarboxylic acids and dicarboxylic acids. Examples of the monocarboxylic acids include acrylic acid, methacrylic acid, and crotonic acid. Examples of the dicarboxylic acids include maleic acid, fumaric acid, and itaconic acid.
[0106] Examples of the monomer having a sulfonic acid group include vinyl sulfonic acid, methylvinyl sulfonic acid, (meth)allyl sulfonic acid, ethyl (meth)acrylate-2-sulfonate, 2-acrylamido-2-methylpropanesulfonic acid, and 3-allyloxy-2-hydroxypropanesulfonic acid.
[0107] In addition, in this specification, "(meth)allyl group" means an allyl group and / or a methallyl group.
[0108] Examples of the monomer having a phosphoric acid group include 2-(meth)acryloyloxyethyl phosphate, methyl-2-(meth)acryloyloxyethyl phosphate, and ethyl-(meth)acryloyloxyethyl phosphate.
[0109] In addition, in this specification, "(meth)acryloyl group" means an acryloyl group and / or a methacryloyl group.
[0110] Examples of the monomer having a hydroxyl group include 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate.
[0111] These acid group-containing monomers may be used alone or in combination of two or more at any ratio.
[0112] The content of the acid group-containing monomer unit in the polymer A is preferably 0.05% by mass or more, more preferably 0.1% by mass or more, and further preferably 0.15% by mass or more, and is preferably 2% by mass or less, more preferably 1% by mass or less, and further preferably 0.5% by mass or less, when all repeating units in the polymer A are taken as 100% by mass.
[0113] -Fluorine-containing monomer units- Examples of the fluorine-containing monomer capable of forming the fluorine-containing monomer unit include, but are not particularly limited to, vinylidene fluoride, tetrafluoroethylene, hexafluoropropylene, chlorotrifluoroethylene, vinyl fluoride, and perfluoroalkyl vinyl ether, etc. In particular, vinylidene fluoride is preferred.
[0114] These fluorine atom-containing monomers may be used alone or in combination of two or more at any ratio.
[0115] In the case where polymer A includes fluorine-containing atom monomer units, from the viewpoint of being able to ensure the better adhesion of functional layer, particulate polymer is preferably a fluorine-containing atom polymer using vinylidene fluoride as a fluorine-containing atom monomer. As fluorine-containing atom polymer, particularly preferably (i) homopolymer of vinylidene fluoride, (ii) copolymer of vinylidene fluoride and other fluorine-containing atom monomers that can be copolymerized with the vinylidene fluoride, (iii) vinylidene fluoride, other fluorine-containing atom monomers that can be copolymerized with the vinylidene fluoride, and copolymer of monomers that can copolymerize with them. And, in fluorine-containing atom polymer, preferably polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), polyvinyl fluoride and tetrafluoroethylene and perfluoroalkyl vinyl ether copolymer.
[0116] -Other monomer units- Polymer A may also contain other monomer units other than aromatic monovinyl monomer units, crosslinkable monomer units, (meth)acrylate monomer units, acid group-containing monomer units and fluorine atom-containing monomer units. Here, other monomer units are not particularly limited, and examples thereof include nitrile group-containing monomer units.
[0117] Examples of nitrile group-containing monomers that can form nitrile group-containing monomer units include α,β-ethylenically unsaturated nitrile monomers. Specifically, the α,β-ethylenically unsaturated nitrile monomers are not particularly limited as long as they are α,β-ethylenically unsaturated compounds having nitrile groups, and examples thereof include acrylonitrile; α-halogenated acrylonitriles such as α-chloroacrylonitrile and α-bromoacrylonitrile; α-alkyl acrylonitriles such as methacrylonitrile and α-ethylacrylonitrile, and the like.
[0118] These nitrile group-containing monomers may be used alone or in combination of two or more at any ratio.
[0119] The content ratio of the nitrile group-containing monomer unit in the polymer A is preferably 3% by mass or more, more preferably 4% by mass or more, and further preferably 6% by mass or more, and is preferably 30% by mass or less, more preferably 27% by mass or less, and further preferably 25% by mass or less, when all repeating units in the polymer A are taken as 100% by mass.
[0120] When the content ratio of the nitrile group-containing monomer unit is not less than the above lower limit, the adhesive force of the particulate polymer can be increased, and the peel strength of the functional layer can be increased.
[0121] On the other hand, when the content ratio of the nitrile group-containing monomer unit is equal to or less than the above upper limit, the flexibility of the particulate polymer can be improved.
[0122] The content of the monomer units other than the nitrile group-containing monomer units in the polymer A is preferably 0 mass % or more, preferably 10 mass % or less, more preferably 7 mass % or less, and further preferably 5 mass % or less, when all repeating units in the polymer A are taken as 100 mass %.
[0123] When the content ratio of other monomer units is equal to or less than the above upper limit, a decrease in the stability of the composition for a functional layer can be suppressed.
[0124] The content of the particulate polymer in the functional layer composition is preferably 5% by mass or more, more preferably 10% by mass or more, and preferably 50% by mass or less, more preferably 40% by mass or less, based on all components (including the dispersion medium) in the functional layer composition.
[0125] If the content of the particulate polymer in the functional layer composition is greater than or equal to the above lower limit, wet adhesiveness and dry adhesiveness can be improved. On the other hand, if the content of the particulate polymer in the functional layer composition is less than or equal to the above upper limit, the storage stability of the functional layer composition can be improved.
[0126] When the functional layer composition contains the binder and non-conductive heat-resistant particles described later, the content ratio of the granular polymer in the functional layer composition is preferably 1 mass % or more and 12 mass % or less relative to the total amount (100 mass %) of the granular polymer, the binder and the non-conductive heat-resistant particles.
[0127] <<Preparation of Particles Comprising Polymer A>> The particles containing polymer A can be prepared by polymerizing a monomer composition containing the above-mentioned monomers in an aqueous solvent such as water. Here, the ratio of each monomer in the monomer composition is usually made the same as the ratio of each monomer unit in polymer A.
[0128] The polymerization method is not particularly limited, and any method such as suspension polymerization, emulsion polymerization coagulation, pulverization, etc. can be used. From the viewpoint of easily adjusting the volume particle size D50 and particle size distribution α of the granular polymer, suspension polymerization and emulsion polymerization coagulation are particularly preferred, and suspension polymerization is more preferred. In addition, as the polymerization reaction, any reaction such as free radical polymerization and living free radical polymerization can also be used.
[0129] -Other compounding agents- The monomer composition used for preparing the pellets containing the polymer A may contain other compounding agents such as a chain transfer agent, a polymerization regulator, a polymerization reaction retarder, a reactive fluidizing agent, a filler, a flame retardant, an antioxidant, a colorant, etc. in any amount.
[0130] Here, as an example, a method for producing particles containing polymer A by suspension polymerization will be described.
[0131] -Preparation of particles comprising polymer A by suspension polymerization method- (1) Preparation of monomer composition First, monomers constituting the desired polymer A and other compounding agents added as necessary are mixed to prepare a monomer composition.
[0132] (2) Droplet formation Next, the monomer composition is dispersed in water, a polymerization initiator is added, and then droplets of the monomer composition are formed. Here, the droplets can be formed by shearing and stirring water containing the monomer composition using a disperser such as an emulsifying disperser.
[0133] When a disperser is used to form droplets, the speed of the disperser is preferably greater than 8000 rpm, more preferably 9500 rpm or more, further preferably 11000 rpm or more, preferably less than 15000 rpm, more preferably 14000 rpm or less, further preferably 13000 rpm or less. If the speed of the disperser is within the above range, the ratio of the volume particle diameter D50 and the particle size distribution α of the granular polymer can be easily adjusted.
[0134] When a disperser is used to form droplets, the stirring speed of the disperser is preferably 21 m / s or more, more preferably 25 m / s or more, further preferably 29 m / s or more, preferably 40 m / s or less, more preferably 37 m / s or less, further preferably 35 m / s or less.
[0135] When the stirring speed of the disperser is within the above range, the ratio of the volume particle diameter D50 and the particle size distribution α of the particulate polymer can be easily adjusted.
[0136] In this specification, the term "stirring speed" refers to the peripheral speed of the outer circumference formed when the dispersing teeth, stirring blades, etc. rotate.
[0137] Examples of the polymerization initiator include oil-soluble polymerization initiators such as tert-butyl peroxy-2-ethylhexanoate and azobisisobutyronitrile. The polymerization initiator may be added after the monomer composition is dispersed in water and before droplets are formed, or may be added to the monomer composition before it is dispersed in water.
[0138] When the particles containing the polymer A are prepared by an emulsion polymerization coagulation method, a water-soluble polymerization initiator such as potassium persulfate can be used as the polymerization initiator.
[0139] From the viewpoint of stabilizing the droplets of the formed monomer composition in water, it is preferred to add a dispersion stabilizer to water to form the droplets of the monomer composition. In this case, as the dispersion stabilizer, for example, metal hydroxides such as magnesium hydroxide, sodium dodecylbenzenesulfonate, etc. can be used. Here, the dispersion stabilizer can be added in the state of a colloidal dispersion in which the dispersion stabilizer is dispersed in water.
[0140] (3) Aggregation Next, after the droplets of the monomer composition are formed, the water containing the formed droplets is heated to initiate polymerization, thereby forming particles containing the polymer A in the water. At this time, the reaction temperature of the polymerization is preferably 50° C. or higher and 95° C. or lower. In addition, the reaction time of the polymerization is preferably 1 hour or longer, preferably 10 hours or shorter, more preferably 8 hours or shorter, and further preferably 6 hours or shorter.
[0141] (4) Cleaning, filtering, dehydration and drying processes After the polymerization is completed, the particles containing the polymer A can be obtained by washing, filtering and drying the water containing the particles containing the polymer A according to a conventional method.
[0142] <<Polymerization initiator decomposition products>> The particles constituting the granular polymer may contain decomposition products of the polymerization initiator used in the polymerization of the polymer A (hereinafter also referred to as "polymerization initiator decomposition products"). In addition, the polymerization initiator decomposition products include not only decomposition products that exist directly after the polymerization reaction, but also products after post-treatment such as decarbonation treatment and denitrification treatment.
[0143] Here, when tert-butyl peroxy-2-ethylhexanoate is used as the polymerization initiator, examples of the polymerization initiator decomposition products include heptyl tert-butyl ether, etc. In addition, when azobisisobutyronitrile is used as the polymerization initiator, examples of the polymerization initiator decomposition products include tetramethylsuccinic acid nitrile, 2-cyanopropane, etc. Furthermore, when potassium persulfate is used as the polymerization initiator, examples of the polymerization initiator decomposition products include sulfate ions (potassium sulfate), etc.
[0144] The content ratio of the polymerization initiator decomposition products in the particles constituting the particulate polymer is preferably 20 ppm or less, more preferably 10 ppm or less, further preferably 5 ppm or less, and particularly preferably 0 ppm, based on the total mass of the particles.
[0145] If the content of the polymerization initiator decomposition products in the particles is below the upper limit, the anti-blocking property of the functional layer can be improved. In addition, in the electrochemical element, the amount of polymerization initiator decomposition products that can cause the resistance value to increase and dissolve in the electrolyte is reduced, resulting in improved cycle characteristics.
[0146] The content ratio of the polymerization initiator decomposition product in the particles can be adjusted by the purification method and purification conditions when preparing the particulate polymer.
[0147] <Bonding material> The functional layer composition of the present invention preferably further comprises a binder. If the functional layer composition further comprises a binder, powdering can be suppressed and wet adhesiveness and dry adhesiveness can be improved.
[0148] The shape of the bonding material may be granular or non-granular. From the viewpoint of effectively suppressing powder loss, the bonding material is preferably granular. In addition, after the components are bonded to each other via the functional layer formed by the functional layer composition, the bonding material may be granular or in any other shape.
[0149] <<Composition of bonding materials>> The binder material is not particularly limited, and examples thereof include known water-insoluble polymers dispersible in a dispersion medium such as water, for example, binder resins such as thermoplastic elastomers. The thermoplastic elastomer is preferably a conjugated diene polymer or an acrylic polymer (ACL).
[0150] These adhesive materials may be used alone or in combination of two or more at any ratio.
[0151] <<<Acrylic polymer>>> An acrylic polymer refers to a polymer containing a (meth)acrylate monomer unit. The acrylic polymer is not particularly limited, and may contain, in addition to the (meth)acrylate monomer unit, for example, the above-mentioned crosslinking monomer unit, acid group-containing monomer unit, etc. In addition, from the aspect of being able to improve wet adhesiveness and dry adhesiveness, the acrylic polymer preferably contains a (meth)acrylate monomer unit and an acid group-containing monomer unit.
[0152] In addition, since the (meth)acrylic acid ester monomer unit, the crosslinking monomer unit, and the acid group-containing monomer unit have been described above, the description thereof will be omitted below.
[0153] - Ratio of each monomer unit in acrylic polymer - When all repeating units in the polymer constituting the adhesive material are taken as 100 mass %, the proportion of the (meth)acrylate monomer unit in the acrylic polymer is preferably 50 mass % or more, more preferably 55 mass % or more, further preferably 58 mass % or more, preferably 98 mass % or less, more preferably 97 mass % or less, further preferably 96 mass % or less.
[0154] When the ratio of the (meth)acrylic acid ester monomer unit is not less than the above lower limit, wet adhesiveness and dry adhesiveness can be further improved.
[0155] On the other hand, when the ratio of the (meth)acrylic acid ester monomer unit is equal to or less than the above upper limit, the blocking resistance of the functional layer and the cycle characteristics of the electrochemical device can be improved.
[0156] When all repeating units in the polymer constituting the adhesive material are taken as 100% by mass, the proportion of the acid group-containing monomer unit in the acrylic polymer is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, further preferably 0.5% by mass or more, preferably 20% by mass or less, more preferably 10% by mass or less, further preferably 5% by mass or less.
[0157] When the ratio of the acid group-containing monomer unit is not less than the above lower limit, the dispersibility of the adhesive material in the functional layer composition and in the functional layer can be improved, and the wet adhesiveness and dry adhesiveness can be further improved.
[0158] On the other hand, when the ratio of the acid group-containing monomer unit is below the upper limit, the residual moisture content of the functional layer can be reduced, and the blocking resistance of the functional layer and the cycle characteristics of the electrochemical device can be improved.
[0159] When all repeating units in the polymer constituting the adhesive material are taken as 100 mass %, the proportion of the crosslinkable monomer unit in the acrylic polymer is preferably 0.1 mass % or more, more preferably 1.0 mass % or more, and preferably 3.0 mass % or less, more preferably 2.5 mass % or less.
[0160] When the ratio of the crosslinkable monomer unit is not less than the above lower limit, the blocking resistance of the functional layer and the cycle characteristics of the electrochemical device can be improved.
[0161] On the other hand, when the ratio of the crosslinkable monomer unit is equal to or less than the above upper limit, wet adhesiveness and dry adhesiveness can be further improved.
[0162] -Other monomer units in acrylic polymers- The acrylic polymer may also contain other monomer units. As other monomers that can form other monomer units that can be contained in the acrylic polymer, there can be cited: conjugated diene monomers such as 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene; the above-mentioned aromatic monovinyl monomers; the above-mentioned nitrile-containing monomers such as acrylonitrile; olefin monomers such as ethylene and propylene; halogen atom-containing monomers such as vinyl chloride and vinylidene chloride; vinyl ester monomers such as vinyl acetate, vinyl propionate, vinyl butyrate, and vinyl benzoate; vinyl ether monomers such as methyl vinyl ether, ethyl vinyl ether, and butyl vinyl ether; vinyl ketone monomers such as methyl vinyl ketone, ethyl vinyl ketone, butyl vinyl ketone, hexyl vinyl ketone, and isopropenyl vinyl ketone; and heterocyclic vinyl compound monomers such as N-vinyl pyrrolidone, vinyl pyridine, and vinyl imidazole. As other monomers, acrylonitrile is particularly preferred.
[0163] These other monomers may be used alone or in combination of two or more at any ratio. The content ratio of the other monomer units in the acrylic polymer may be appropriately adjusted.
[0164] When all repeating units in the polymer constituting the adhesive material are taken as 100 mass %, the proportion of other monomer units in the acrylic polymer is preferably less than 30 mass %, more preferably less than 15 mass %, and further preferably 10 mass % or less.
[0165] <<<Conjugated Diene Polymers>>> Conjugated diene polymer refers to a polymer comprising a conjugated diene monomer unit. Moreover, as a specific example of a conjugated diene polymer, it is not particularly limited, and copolymers comprising aromatic monovinyl monomer units and conjugated diene monomer units such as styrene-butadiene copolymer (SBR), butadiene rubber (BR), acrylic rubber (NBR) (comprising a copolymer of acrylonitrile units and butadiene units) and their hydrogenated products etc. can be enumerated.
[0166] In addition, since the conjugated diene monomer unit and the aromatic monovinyl monomer unit have been described above, the description thereof will be omitted below.
[0167] - Ratio of each monomer unit in the conjugated diene polymer - When all repeating units in the polymer constituting the adhesive material are taken as 100% by mass, the proportion of the conjugated diene monomer units in the conjugated diene polymer is preferably 15% by mass or more, more preferably 30% by mass or more, preferably 80% by mass or less, more preferably 60% by mass or less, and further preferably 40% by mass or less.
[0168] When all repeating units in the polymer constituting the adhesive material are taken as 100% by mass, the proportion of the aromatic monovinyl monomer unit in the conjugated diene polymer is preferably 15% by mass or more, more preferably 35% by mass or more, further preferably 55% by mass or more, preferably 80% by mass or less, and more preferably 70% by mass or less.
[0169] -Other monomer units in the conjugated diene polymer- The conjugated diene polymer may contain other monomer units. Examples of other monomers that can form other monomer units that can be contained in the conjugated diene polymer include the above-mentioned acid group-containing monomers and the above-mentioned nitrile group-containing monomers.
[0170] These other monomers may be used alone or in combination of two or more at any ratio. The content ratio of the other monomer units in the conjugated diene polymer may be adjusted appropriately.
[0171] <<Glass transition temperature of adhesive material>> The glass transition temperature (Tg) of the adhesive material is preferably -100°C or higher, more preferably -90°C or higher, further preferably -80°C or higher, preferably lower than 30°C, more preferably 20°C or lower, further preferably 15°C or lower.
[0172] When the glass transition temperature of the adhesive material is not less than the above lower limit, wet adhesiveness and dry adhesiveness can be further improved. In addition, the blocking resistance of the functional layer can be improved.
[0173] On the other hand, when the glass transition temperature of the binder is equal to or lower than the upper limit described above, the flexibility of the functional layer can be further improved.
[0174] <<Volume particle size D50 of bonding material>> The volume particle size D50 of the binder material is preferably 0.1 μm or more, more preferably 0.2 μm or more, and is preferably 0.8 μm or less, more preferably 0.5 μm or less.
[0175] When the volume particle size D50 of the binder material is equal to or larger than the above lower limit, it is possible to further suppress a decrease in ion conductivity in the functional layer, thereby improving the electrochemical characteristics (particularly output characteristics) of the electrochemical device.
[0176] On the other hand, when the volume particle size D50 of the adhesive material is equal to or less than the upper limit, the wet adhesiveness and the dry adhesiveness can be further improved.
[0177] In addition, in this specification, the volume particle size D50 of the adhesive material refers to the particle size at which the cumulative volume calculated from the small particle size side in the particle size distribution (volume basis) obtained by using a laser diffraction method becomes 50%, and can be measured according to the method described in the examples of this specification.
[0178] <<Content of bonding material>> The content of the binder in the functional layer composition is preferably 20 parts by mass or more, more preferably 40 parts by mass or more, further preferably 50 parts by mass or more, preferably 80 parts by mass or less, more preferably 70 parts by mass or less, further preferably 60 parts by mass or less, relative to 100 parts by mass of the granular polymer.
[0179] When the content of the binder is not less than the above lower limit, powdering is suppressed, and as a result, wet adhesiveness and dry adhesiveness can be further improved.
[0180] On the other hand, when the content of the binder material is equal to or less than the upper limit, a decrease in the ion conductivity of the functional layer can be suppressed, and a decrease in the output characteristics of the obtained electrochemical element can be suppressed.
[0181] When the functional layer composition contains the non-conductive heat-resistant particles described later, the content of the binder in the functional layer composition is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, further preferably 0.5 parts by mass or more, further preferably 3 parts by mass or more, and preferably 20 parts by mass or less, more preferably 15 parts by mass or less, further preferably 10 parts by mass or less, relative to 100 parts by mass of the non-conductive heat-resistant particles.
[0182] When the content of the binder is not less than the above lower limit, powdering is suppressed, and as a result, wet adhesiveness and dry adhesiveness can be further improved.
[0183] On the other hand, when the content of the binder material is equal to or less than the upper limit, a decrease in the ion conductivity of the functional layer can be suppressed, and a decrease in the output characteristics of the obtained electrochemical element can be suppressed.
[0184] The binder is not particularly limited and can be prepared by, for example, polymerizing a monomer composition containing the above monomers in an aqueous solvent such as water. Here, the ratio of each monomer in the monomer composition is usually the same as the ratio of each monomer unit in the binder.
[0185] The polymerization method and polymerization reaction are not particularly limited, and for example, the polymerization method and polymerization reaction exemplified in the polymerization method of the above-mentioned particulate polymer can be used.
[0186] <Non-conductive heat-resistant particles> The composition for a functional layer of the present invention preferably further comprises non-conductive heat-resistant particles (hereinafter also referred to as “heat-resistant particles”). If the composition for a functional layer further comprises heat-resistant particles, the heat resistance of the functional layer can be improved.
[0187] In this specification, "non-conductive heat-resistant particles" refer to non-conductive fine particles having a heat-resistant temperature of 200° C. or higher, and "heat-resistant temperature" refers to a temperature at which no substantial physical changes such as thermal deformation occur.
[0188] The heat-resistant particles are not particularly limited as long as they are fine particles having a heat-resistant temperature of 200° C. or higher, are electrochemically stable, and have electrical insulating properties, but inorganic particles are preferred.
[0189] Since inorganic particles have a relatively large specific gravity, when a functional layer is formed by coating a functional layer composition containing inorganic particles on a substrate, the granular polymer becomes more likely to protrude relative to the inorganic particles on the surface of the functional layer in the thickness direction, resulting in improved wet adhesion and dry adhesion.
[0190] Here, as the material of the inorganic particles, it is preferred that it is stably present and electrochemically stable under the use environment of the electrochemical element, and examples thereof include: oxide particles such as aluminum oxide (alumina), aluminum oxide hydrate (boehmite (AlOOH)), gibbsite (Al(OH)3), silicon oxide, magnesium oxide (magnesia), magnesium hydroxide, calcium oxide, titanium oxide (titania), barium titanate (BaTiO3), zirconium oxide (ZrO), and aluminum oxide-silicon dioxide composite oxide; nitride particles such as aluminum nitride and boron nitride; covalently bonded crystal particles such as silicon and diamond; insoluble ionic crystal particles such as barium sulfate, calcium fluoride, and barium fluoride; clay particles such as talc and montmorillonite, etc. Among these, aluminum oxide, aluminum oxide hydrate (boehmite), magnesium hydroxide, and barium sulfate are more preferred, and aluminum oxide is further preferred. In addition, element replacement, surface treatment, solid solution, etc. can be implemented on these particles as needed.
[0191] These inorganic particles may be used alone or in combination of two or more at any ratio.
[0192] <<Volume particle size D50 of heat-resistant particles>> The volume particle size D50 of the heat-resistant particles is preferably 0.1 μm or more, more preferably 0.2 μm or more, further preferably 0.25 μm or more, and is preferably 1.5 μm or less, more preferably 1.0 μm or less, further preferably 0.8 μm or less.
[0193] When the volume particle size D50 of the heat-resistant particles is greater than or equal to the above lower limit, the heat-resistant particles are densely packed in the functional layer, thereby further suppressing the reduction of ion conductivity in the functional layer and improving the electrochemical characteristics (particularly output characteristics) of the electrochemical element.
[0194] On the other hand, when the volume particle size D50 of the heat-resistant particles is equal to or less than the upper limit, the functional layer can exhibit excellent heat resistance even when the functional layer is made thin, so the capacity of the electrochemical device can be increased.
[0195] In this specification, the volume particle size D50 of the heat-resistant particles refers to a particle size at which the cumulative volume calculated from the small particle size side in the particle size distribution (volume basis) measured by laser diffraction method is 50%, and can be measured by the method described in the Examples.
[0196] <<Ratio of granular polymer to heat-resistant particles>> The volume ratio of the granular polymer to the heat-resistant particles in the functional layer composition (volume of the granular polymer / volume of the heat-resistant particles) is preferably 5 / 95 or more, more preferably 20 / 80 or more, further preferably 25 / 75 or more, further preferably 30 / 70 or more, preferably 45 / 55 or less, more preferably 40 / 60 or less, further preferably 35 / 65 or less.
[0197] When the volume ratio of the particulate polymer to the heat-resistant particles is within the above range, the balance between the heat resistance and the adhesiveness of the functional layer becomes good.
[0198] In addition, the mass ratio of the granular polymer to the heat-resistant particles in the functional layer composition (mass of the granular polymer / mass of the heat-resistant particles) is preferably 1 / 99 or more, more preferably 6 / 94 or more, further preferably 9 / 91 or more, preferably 51 / 49 or less, more preferably 42 / 58 or less, further preferably 36 / 64 or less.
[0199] When the mass ratio of the particulate polymer to the heat-resistant particles is within the above range, the balance between the heat resistance and the adhesiveness of the functional layer becomes favorable.
[0200] <Amine compounds> The functional layer composition of the present invention preferably further contains an amine compound. If the functional layer composition further contains an amine compound, corruption of the functional layer composition can be suppressed, thereby improving the storage stability of the functional layer composition.
[0201] Here, as amine compound, it is not particularly limited, for example, hydroxylamine sulfate, diethylhydroxylamine, dimethylhydroxylamine, dipropylhydroxylamine, isopropylhydroxylamine, isothiazolinyl compounds, etc. can be mentioned. From the aspect of being able to further improve the storage stability of the composition for functional layer, isothiazolinyl compounds are particularly preferred. In addition, as isothiazolinyl compounds, for example, 1,2-benzo-4-isothiazoline-3-one, 2-methyl-4-isothiazoline-3-one, etc. can be mentioned.
[0202] These amine compounds may be used alone or in combination of two or more at any ratio.
[0203] The content of the amine compound is preferably 0.3 parts by mass or more, more preferably 0.5 parts by mass or more, and is preferably 2 parts by mass or less, more preferably 1 part by mass or less, based on 100 parts by mass of the particulate polymer.
[0204] <Other ingredients> The composition for the functional layer may contain any other components in addition to the granular polymer, the binder, the non-conductive heat-resistant particles and the amine compound. The other components are not particularly limited as long as they do not affect the electrochemical reaction in the electrochemical element, and examples thereof include known additives such as dispersants, viscosity modifiers, and wetting agents. These other components may be used alone or in combination of two or more.
[0205] <Method for preparing composition for electrochemical element functional layer> The preparation method of the composition for the functional layer is not particularly limited, and it can be prepared by, for example, mixing the above-mentioned granular polymer, water as a dispersion medium, a binder material used as needed, heat-resistant particles, an amine compound, and other components. In addition, when the granular polymer and the binder material are prepared by polymerizing the monomer composition in an aqueous solvent, the granular polymer and the binder material can be directly mixed with other components in the state of an aqueous dispersion. In addition, when the granular polymer and the binder material are mixed in the state of an aqueous dispersion, the water in the aqueous dispersion can be used as the dispersion medium.
[0206] Here, the mixing method of the above-mentioned components is not particularly limited. In order to disperse the components efficiently, it is preferred to use a dispersing machine as a mixing device for mixing. Moreover, the dispersing machine is preferably a device that can evenly disperse and mix the above-mentioned components. As the dispersing machine, a ball mill, a sand mill, a pigment dispersing machine, a grinding machine, an ultrasonic dispersing machine, a homogenizer, a planetary mixer, etc. can be cited.
[0207] (Laminate for electrochemical device) The electrochemical element laminate of the present invention comprises a substrate and a functional layer formed on the substrate, and the functional layer is formed using the functional layer composition of the present invention. Since the functional layer composition of the present invention can form a functional layer with excellent wet adhesion, as long as it is a laminate having a functional layer formed using the functional layer composition of the present invention, the cycle characteristics of the electrochemical element having the laminate can be improved.
[0208] <Base Material> The substrate is not particularly limited. For example, when the functional layer is used as a component constituting a part of the separator, the separator substrate can be used as the substrate, and when the functional layer is used as a component constituting a part of the electrode, the electrode substrate formed by forming an electrode composite material layer on the current collector can be used as the substrate. The usage of the laminate obtained by forming the functional layer on the substrate using the functional layer composition is not particularly limited. For example, the functional layer can be formed on the separator substrate and directly used as an electrochemical element component such as a separator, or the functional layer can be formed on the electrode substrate and directly used as an electrode.
[0209] <<Spacer Base Material>> As the spacer substrate forming the functional layer, there is no particular limitation, and the spacer substrate described in, for example, Japanese Patent Publication No. 2012-204303 can be used. Among these, from the aspect of being able to thin the overall film thickness of the spacer, thereby being able to increase the ratio of the electrode active material in the electrochemical element and thus increase the capacity per unit volume, it is preferably a microporous film formed by a polyolefin-based (polyethylene, polypropylene, polybutylene, polyvinyl chloride) resin. In addition, the spacer substrate can include any layer other than the functional layer in a part thereof that can play a desired function.
[0210] <<Electrode Base Material>> As the electrode substrate (positive electrode substrate and negative electrode substrate) forming the functional layer, it is not particularly limited, and an electrode substrate having an electrode composite material layer formed on the current collector can be cited. Here, the components in the current collector and the electrode composite material layer (for example, electrode active material (positive electrode active material, negative electrode active material) and electrode composite material layer binding material (positive electrode composite material layer binding material, negative electrode composite material layer binding material) etc.), and the method for forming the electrode composite material layer on the current collector can use known ones, and those described in, for example, Japanese Patent Publication No. 2013-145763 can be used. In addition, the electrode substrate can include any layer having a desired function in a part thereof except the functional layer.
[0211] <Functional Layer> The functional layer can be formed on the above-mentioned substrate using the composition for the functional layer of the present invention. Here, the functional layer contains at least: the above-mentioned granular polymer; a binder material and heat-resistant particles used as needed; an amine compound; and other components. In addition, the components contained in the functional layer are the components contained in the above-mentioned composition for the functional layer, and the preferred abundance ratio of these components is the same as the preferred abundance ratio of the components in the composition for the functional layer.
[0212] <<Method for forming functional layer>> The method for forming a functional layer on a substrate using the composition for a functional layer is not particularly limited, and examples thereof include: 1) A method of coating the composition for the functional layer on the surface of the substrate and then drying the composition; 2) A method of immersing the substrate in the composition for the functional layer and then drying the substrate; 3) A method in which a composition for a functional layer is applied onto a release substrate, dried to form a functional layer, and the obtained functional layer is transferred onto the surface of the substrate.
[0213] In addition, the functional layer may be formed on only one surface of the substrate, or may be formed on both surfaces of the substrate.
[0214] Here, the release substrate is not particularly limited, and a known release substrate can be used.
[0215] Among these, the method 1) is preferred because the thickness of the functional layer can be easily controlled. Furthermore, the method 1) may include, for example, a step of applying a composition for a functional layer on a substrate (coating step); and a step of drying the composition for a functional layer applied on the substrate to form a functional layer (functional layer forming step).
[0216] -Coating process- In the coating step, the method for coating the functional layer composition on the substrate is not particularly limited, and examples thereof include doctor blade method, reverse roll method, direct roll method, gravure method, extrusion method, brush coating method and the like.
[0217] - Functional layer forming process - In the functional layer forming step, the method for drying the functional layer composition on the substrate is not particularly limited, and a known method can be used, for example, drying using warm air, hot air, or low-humidity air; vacuum drying; and drying using irradiation of infrared rays, electron beams, etc. The drying conditions are not particularly limited, but the drying temperature is preferably 50° C. or higher and 150° C. or lower, and the drying time is preferably 1 minute or higher and 30 minutes or lower.
[0218] Furthermore, the functional layer formed on the substrate can be preferably used as a single layer that simultaneously functions as a heat-resistant layer that improves the heat resistance of the substrate and as an adhesive layer that firmly bonds members to each other.
[0219] Furthermore, the substrate having the functional layer formed using the functional layer composition as described above, that is, the laminate of the present invention, can be produced with a further reduced amount of work and time compared to substrates having a conventional heat-resistant layer and an adhesive layer, and thus has high productivity.
[0220] Here, in the functional layer formed using the composition for the functional layer containing heat-resistant particles, a plurality of heat-resistant particles are usually arranged in a stacked manner along the thickness direction of the functional layer. Moreover, the thickness of the layer formed by overlapping the heat-resistant particles in the thickness direction of the functional layer (hereinafter also referred to as the "heat-resistant particle layer") is preferably 0.5 μm or more, more preferably 0.8 μm or more, further preferably 1 μm or more, preferably 6 μm or less, more preferably 5 μm or less, and further preferably 4 μm or less.
[0221] When the thickness of the heat-resistant particle layer is not less than the above lower limit, the heat resistance of the functional layer becomes extremely good.
[0222] On the other hand, when the thickness of the heat-resistant particle layer is equal to or less than the upper limit, the ion diffusibility of the functional layer can be ensured, and the electrochemical characteristics (particularly output characteristics) of the electrochemical element can be further sufficiently improved.
[0223] In addition, in this specification, "the thickness of the heat-resistant particle layer" can be measured using the method described in the examples of this specification.
[0224] <<Ratio of Volume Particle Diameter D50 of Particulate Polymer to Thickness of Heat-Resistant Particle Layer>> The ratio of the volume particle size D50 of the above-mentioned granular polymer to the thickness of the heat-resistant particle layer (volume particle size D50 of the granular polymer / thickness of the heat-resistant particle layer) is preferably greater than 1.05, more preferably greater than 1.2, further preferably greater than 1.5, preferably less than 5.0, more preferably less than 4.5, further preferably less than 4.0.
[0225] If the ratio of the volume particle size D50 of the granular polymer to the thickness of the heat-resistant particle layer is greater than the above lower limit, the granular polymer becomes more likely to protrude relative to the surface of the heat-resistant particles in the thickness direction of the functional layer, thereby being able to exert better wet adhesion and dry adhesion.
[0226] On the other hand, when the ratio of the volume particle size D50 of the particulate polymer to the thickness of the heat-resistant particle layer is below the upper limit, the particulate polymer can be further prevented from falling off when the functional layer composition is applied to the substrate, thereby forming a more uniform functional layer.
[0227] <<Thickness of functional layer>> The thickness of the functional layer formed on the substrate (hereinafter also referred to as the "maximum thickness of the functional layer") is preferably greater than 1.0 μm, more preferably greater than 1.5 μm, further preferably greater than 2.0 μm, particularly preferably greater than 2.5 μm, most preferably greater than 5.0 μm, preferably less than 10.0 μm, more preferably less than 9.0 μm, and further preferably less than 8.0 μm.
[0228] When the maximum thickness of the functional layer is not less than the above lower limit, the heat resistance of the functional layer becomes extremely good.
[0229] On the other hand, when the maximum thickness of the functional layer is equal to or less than the upper limit, the ion diffusibility of the functional layer can be ensured, and the electrochemical characteristics (particularly output characteristics) of the electrochemical device can be further sufficiently improved.
[0230] In the present specification, the “maximum thickness of the functional layer” can be measured using, for example, a field emission scanning electron microscope (FE-SEM).
[0231] (Electrochemical Components) The electrochemical device of the present invention includes the laminate of the present invention. Such an electrochemical device can exhibit excellent cycle characteristics.
[0232] Furthermore, the electrochemical device of the present invention is only required to have at least the laminate of the present invention, and therefore may have constituent elements other than the laminate of the present invention unless the effects of the present invention are significantly impaired.
[0233] Furthermore, the electrochemical device of the present invention is not particularly limited, and is, for example, a lithium ion secondary battery or an electric double layer capacitor, and is preferably a lithium ion secondary battery.
[0234] Here, a lithium ion secondary battery as an example of an electrochemical element of the present invention is described below. The lithium ion secondary battery of the present invention has the above-mentioned laminate of the present invention. More specifically, the lithium ion secondary battery has a positive electrode, a negative electrode, a separator with a functional layer formed on a separator substrate (laminate of the present invention) and an electrolyte. The functional layer can be formed only on a single side of the separator substrate, or on both sides of the separator substrate.
[0235] In addition, in the following example, the functional layer is formed on the separator substrate, but the functional layer may also be formed on the electrode substrate.
[0236] Moreover, in the lithium ion secondary battery of the present invention, the positive electrode and the separator substrate, and / or the negative electrode and the separator substrate are firmly bonded in the electrolyte through the functional layer. Therefore, the distance between the pole plates of the electrode is also suppressed from expanding with repeated charge and discharge, and the battery characteristics such as cycle characteristics become good. In addition, in the lithium ion secondary battery, the heat resistance of the separator substrate is improved through the functional layer. Furthermore, the lithium ion secondary battery can shorten the time required for manufacturing the separator compared with the case of using an existing separator with a heat-resistant layer and an adhesive layer, and can be manufactured with high productivity.
[0237] In addition, as the above-mentioned positive electrode, negative electrode, and electrolyte solution, known positive electrode, negative electrode, and electrolyte solution used in lithium ion secondary batteries can be used.
[0238] <Positive and negative electrodes> Specifically, as an electrode (positive electrode and negative electrode), an electrode formed by forming an electrode composite material layer on a current collector can be used. In addition, as a current collector, a current collector formed of metal materials such as iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, platinum, etc. can be used. Among these, as a current collector for the negative electrode, a current collector formed of copper is preferably used. In addition, as a current collector for the positive electrode, a current collector formed of aluminum is preferably used. Furthermore, as an electrode composite material layer, a layer comprising an electrode active material and a binder can be used.
[0239] <Separator with functional layer (laminate)> The separator with a functional layer can be produced by, for example, forming a functional layer on a separator substrate using the method for forming the functional layer described above.
[0240] Here, as the separator substrate, there is no particular limitation, and for example, the separator substrate described in Japanese Patent Publication No. 2012-204303 can be used. Among these, from the viewpoint of being able to thin the overall film thickness of the separator with the functional layer, thereby being able to increase the ratio of the electrode active material in the lithium ion secondary battery and thus increasing the capacity per unit volume, a microporous membrane formed of a polyolefin resin (polyethylene, polypropylene, polybutylene, polyvinyl chloride) is preferred.
[0241] <Electrolyte> As the electrolyte, an organic electrolyte in which a supporting electrolyte is dissolved in an organic solvent is generally used. As a supporting electrolyte, for example, a lithium salt can be used in a lithium ion secondary battery. As a lithium salt, for example, LiPF6, LiAsF6, LiBF4, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, (C2F5SO2)NLi, etc. can be cited. Since it is easily soluble in a solvent and shows a high degree of dissociation, LiPF6, LiClO4, and CF3SO3Li are particularly preferred. In addition, the electrolyte can be used alone or in combination of two or more. Generally, there is a tendency that the higher the degree of dissociation of the supporting electrolyte, the higher the lithium ion conductivity, so the lithium ion conductivity can be adjusted by the type of supporting electrolyte.
[0242] As an organic solvent used in the electrolyte, there is no particular limitation as long as it is a solvent that can dissolve the supporting electrolyte. For example, in a lithium ion secondary battery, preferably used are: carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), ethyl methyl carbonate (ethyl methyl carbonate (EMC)), and vinylene carbonate; esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfur-containing compounds such as cyclopentane and dimethyl sulfoxide, etc.
[0243] In addition, a mixed solution of these organic solvents can also be used. Carbonates are particularly preferred because of their high dielectric constant and wide stable potential region. Generally, there is a tendency that the lower the viscosity of the organic solvent used, the higher the lithium ion conductivity, so the lithium ion conductivity can be adjusted according to the type of organic solvent.
[0244] The concentration of the electrolyte in the electrolytic solution can be adjusted appropriately. In addition, a known additive may be added to the electrolytic solution.
[0245] <Method for producing lithium-ion secondary battery> The lithium ion secondary battery as the electrochemical element of the present invention can be made by, for example, overlapping the above-mentioned positive and negative electrodes across a spacer (laminate of the present invention) with a functional layer, winding it, folding it, etc. as needed, and placing it in a battery container, and injecting the electrolyte into the battery container for sealing. Here, porous metal mesh, fuse, PTC element and other anti-overcurrent elements, guide plates, etc. can also be placed in the battery container as needed to prevent the pressure inside the battery from rising and overcharging and discharging. The shape of the battery can be any one of, for example, coin-type, button-type, sheet-type, cylindrical, square, flat, etc.
[0246] Example Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. In addition, in the following description, "%" and "part" indicating an amount are based on mass unless otherwise specified.
[0247] In a polymer produced by copolymerizing a plurality of monomers, unless otherwise specified, the proportion of a structural unit formed by polymerizing a certain monomer in the polymer is usually consistent with the ratio (feed ratio) of the certain monomer in all monomers used to polymerize the polymer.
[0248] In the examples and comparative examples, the glass transition temperature, the volume particle size D50 of the granular polymer and the ratio of the particle size distribution α, the volume particle size D50 of the binder material, the volume particle size D50 of the heat-resistant particles, the average roundness and roundness distribution of the granular polymer, the amount of the granular polymer dissolved in THF, the content of the polymerization initiator decomposition product in the particles, the thickness of the heat-resistant particle layer, and the volume ratio of the granular polymer to the heat-resistant particles were measured by the following method. In addition, the wet adhesion, dry adhesion, the anti-blocking property of the functional layer, and the cycle characteristics of the secondary battery were measured and evaluated by the following method.
[0249] <Glass transition temperature> The granular polymer and the binder prepared in the examples and comparative examples were used as the test samples. 10 mg of the test sample was weighed in an aluminum pan, and the differential thermal analysis measuring device ("EXSTARDSC6220" manufactured by SII Nanotechnology) was used to measure the temperature range of -100°C to 500°C and the heating rate of 10°C / min under the conditions specified in JIS Z8703 to obtain a differential scanning calorimetry (DSC) curve. In addition, an empty aluminum pan was used as a reference. In the obtained differential scanning calorimetry (DSC) curve, the intersection of the baseline just before the endothermic peak of the DSC curve where the differential signal (DDSC) becomes 0.05 mW / min / mg or more and the tangent of the DSC curve at the inflection point that first appears after the endothermic peak was taken as the glass transition temperature (°C).
[0250] <Volume particle size D50 and particle size distribution α of granular polymer> The granular polymer prepared in the examples and comparative examples was used as a measurement sample. 0.1 g of the measurement sample was weighed and put into a beaker, and 0.1 mL of an alkylbenzene sulfonic acid aqueous solution (manufactured by Fujifilm Corporation, "DRYWEL") was added as a dispersant. 10 to 30 mL of a diluent (manufactured by Beckman Coulter, Inc., "ISOTON II") was further added to the above beaker, and dispersed for 3 minutes using a 20 W (watt) ultrasonic disperser. Then, a particle size measuring machine (manufactured by Beckman Coulter, Inc., "Multisizer") was used to measure under the conditions of pore size: 20 μm, medium: ISOTON II, and number of measured particles: 100,000. In the particle size distribution (volume basis) of the granular polymer obtained by the measurement, the particle size D50 at which the cumulative volume calculated from the small particle size side becomes 50% is taken as the volume particle size D50 of the granular polymer.
[0251] Furthermore, the value of volume particle diameter D50×1.5 was calculated from the value of volume particle diameter D50, and the proportion of particles having a particle diameter greater than the value of volume particle diameter D50×1.5 (proportion of large particles) was determined, taking the particulate polymer as 100% by volume.
[0252] Furthermore, the value of volume particle diameter D50×3.0 was calculated from the value of volume particle diameter D50, and the proportion of particles having a particle diameter greater than the value of volume particle diameter D50×3.0 (proportion of coarse particles) was determined, taking the particulate polymer as 100% by volume.
[0253] <Volume particle size D50 of bonding material> The volume particle size D50 of the adhesive material prepared in the embodiment is measured by a laser diffraction method. Specifically, an aqueous dispersion solution (solid content concentration adjusted to 0.1% by mass) containing the prepared adhesive material is used as a sample. Then, a laser diffraction particle size distribution measuring device (manufactured by Beckman Coulter Co., Ltd., "LS-230") is used for measurement. In the particle size distribution (volume basis) of the adhesive material obtained by the measurement, the particle size D50 at which the cumulative volume calculated from the small particle size side becomes 50% is used as the volume particle size D50 of the adhesive material.
[0254] <Volume particle size D50 of heat-resistant particles> The volume particle size D50 of the heat-resistant particles used in Examples and Comparative Examples was measured by a laser diffraction method.
[0255] Specifically, in the particle size distribution (volume basis) of the heat-resistant particles measured by laser diffraction method, the particle size (D50) at which the cumulative volume calculated from the smaller particle size side becomes 50% is defined as the volume particle size D50 of the heat-resistant particles.
[0256] <Average Circularity and Circularity Distribution of Granular Polymer> The granular polymer prepared in the examples and comparative examples was used as a test sample. 10 mL of ion exchange water was pre-added in a container, 0.02 g of a surfactant (alkylbenzene sulfonic acid) as a dispersant was added thereto, and 0.02 g of the test sample was further added, and a dispersion treatment of 60 W (watt) and 3 minutes was performed using an ultrasonic disperser. The concentration of the test sample during the measurement was adjusted to 3000 to 10000 pieces / μL, and 1000 to 10000 test samples with an equivalent circle diameter of 0.4 μm or more were measured using a flow particle image analyzer (manufactured by Sysmex Corporation, "FPIA-3000"). In addition, the roundness is shown by the following formula (I), and the average roundness is taken as the average value.
[0257]
[0258] In addition, for the particulate polymer, the ratio of particles having a circularity of less than 0.95 was determined on a number basis.
[0259] <Amount of granular polymer dissolved in THF> The aqueous dispersion of the granular polymer prepared in the examples and comparative examples was filtered and separated using filter paper No. 5B (manufactured by Advantech Corporation) for quantitative analysis, and the obtained solid component was placed in a container of a dryer and dried at 40°C for 48 hours to obtain a dried granular polymer. About 0.2 g of the obtained powder was pressed at 200°C and 5 MPa for 2 minutes to obtain a membrane. Then, the dried membrane was cut into 3 to 5 mm squares and accurately weighed to about 1 g. The mass of the membrane obtained by cutting was taken as w0. The membrane was immersed in 50 g of tetrahydrofuran (THF) at 25°C for 24 hours. Thereafter, the membrane lifted out of THF was vacuum dried at a temperature of 105°C for 3 hours, and the mass w1 of the insoluble component was measured. Then, the elution amount was calculated using the following calculation formula.
[0260]
[0261] <Content of Polymerization Initiator Decomposition Products in Pellets> The aqueous dispersion of the granular polymer prepared in the examples and comparative examples was separated by filtration using a quantitative analysis filter paper No. 5B (manufactured by Advantech Corporation), and the obtained solid content was placed in a container of a dryer and dried at 40°C for 48 hours to obtain a dried granular polymer. About 1.0 g of the obtained powder was mixed with 5 g of acetone and allowed to stand at room temperature (25°C) for 15 hours to extract the polymerization initiator decomposition product in acetone. Thereafter, the acetone containing the polymerization initiator decomposition product was filtered using a 0.45 μm PTFE filter. 1 μL was accurately measured using a microsyringe, and the following gas chromatography was used for measurement to determine the content ratio of the polymerization initiator decomposition product in the particles relative to the total mass of the particles constituting the granular polymer. In addition, in the suspension polymerization method of the examples and comparative examples, since tert-butyl peroxy-2-ethylhexanoate was used as the polymerization initiator, the polymerization initiator decomposition product was heptyl tert-butyl ether.
[0262] [Gas chromatography] Device: 8860 made by Agilent Chromatographic column: DB-1 0.25mm×30m manufactured by Agilent Analytical conditions: injector 250℃, detector 300℃ Temperature program: After the sample is injected, it is kept at 50°C for 5 minutes, then the temperature is increased to 280°C at a rate of 10°C / min, and kept at 280°C for 10 minutes.
[0263] Here, in Example 6, the content ratio of the polymerization initiator decomposition product was determined by the following method.
[0264] Specifically, the aqueous dispersion of the granular polymer prepared in Example 6 was separated by filtration using a quantitative analysis filter paper No. 5B (manufactured by Advantech Corporation), and the obtained solid content was placed in a container of a dryer and dried at 40°C for 48 hours to obtain a dried granular polymer. About 1.0 g of the obtained powder was mixed with 5 g of water, and allowed to stand at room temperature (25°C) for 15 hours to extract the polymerization initiator decomposition product in the water. Thereafter, the water containing the polymerization initiator decomposition product was filtered using a 0.45 μm PTFE filter. The obtained solution (water) was used to determine the content ratio of the polymerization initiator decomposition product in the particles relative to the total mass of the particles constituting the granular polymer using an ion chromatograph (manufactured by Thermo Fisher Scientific, product name: Integrion RFIC). In addition, in the emulsion polymerization coagulation method of Example 6, since potassium persulfate was used as the polymerization initiator, the polymerization initiator decomposition product was sulfate ion.
[0265] <Thickness of Heat-resistant Particle Layer> The cross section of the spacer (laminated body) with the functional layer is observed using a field emission scanning electron microscope (FE-SEM), and the thickness of the heat-resistant particle layer is calculated from the obtained image. In addition, the thickness of the heat-resistant particle layer is the distance in the vertical direction from the surface of the spacer on the side where the functional layer is formed to the heat-resistant particles on the surface forming the functional layer.
[0266] <Volume Ratio of Granular Polymer to Heat-Resistant Particles> The volume ratio of the granular polymer to the heat-resistant particles (volume of the granular polymer / volume of the heat-resistant particles) was determined from the feed amounts of the heat-resistant particles and the granular polymer when preparing the slurry composition (composition for the functional layer). 3 The density of boehmite is 3.1 g / cm 3 The density of magnesium hydroxide is 2.4 g / cm 3 , the density of barium sulfate is 4.5g / cm 3 to perform the calculation.
[0267] <Adhesion after electrolyte immersion (wet adhesion)> The positive electrode and the separator with a functional layer (having a functional layer on both sides) prepared in the examples and comparative examples were cut into a length of 50 mm and a width of 10 mm, respectively. Then, the cut positive electrode and separator were overlapped and stacked. Using a roller press at a temperature of 25°C and a load of 10 kN / m, the obtained laminated sheet was pressed at a pressing speed of 30 m / min to obtain a test piece. The test piece was immersed in an electrolyte at a temperature of 60°C for 72 hours. Here, as an electrolyte, a solution containing LiPF6 at a concentration of 1 M as a supporting electrolyte in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) (volume mixing ratio: EC / DEC=1 / 2) was used. The immersed test piece was taken out of the electrolyte and the electrolyte on the surface of the test piece was wiped off. The test piece was pressed again under the conditions of 1 MPa, 80°C, and 3 minutes. The test piece after being pressed again is pasted with a transparent tape (transparent tape specified in JIS Z1522) on the surface of the positive electrode in a manner that the collector side of the positive electrode faces downward. In addition, the transparent tape is fixed to a horizontal test bench in advance. Then, one end of the spacer is stretched vertically upward at a tensile speed of 50 mm / min to measure the stress during peeling. The measurement is performed three times in total. In addition, a laminate of a negative electrode and a spacer is obtained in the same manner as above, and the laminate is pressed to obtain a test piece. Then, the test piece after being pressed again is obtained in the same manner as the case of using the above-mentioned positive electrode, and the stress after being immersed in the electrolyte is measured three times in total.
[0268] By using the above-mentioned positive electrode and negative electrode measurements, the average value of the stress obtained in total of six times was obtained as the peel strength (N / m), and the adhesion (wet adhesion) between the electrode and the separator through the functional layer after electrolyte immersion was evaluated according to the following criteria. The greater the peel strength, the better the wet adhesion.
[0269] A: Peel strength is 5.0N / m or more B: Peel strength is 3.0 N / m or more and less than 5.0 N / m C: Peel strength is 1.0 N / m or more and less than 3.0 N / m D: Peel strength less than 1.0N / m <Adhesion before electrolyte immersion (dry adhesion)> The negative electrode and the separator with a functional layer (having a functional layer on both sides) prepared in the embodiment and the comparative example were cut into a width of 10 mm and a length of 50 mm, respectively, and the negative electrode and the separator were stacked, and a flat press was used at a temperature of 70°C and a load of 0.5 kN to press for 10 seconds to obtain a test piece. The test piece was pasted with a transparent tape on the surface of the electrode with the current collector side of the negative electrode facing down. At this time, the transparent tape specified in JIS Z1522 was used as the transparent tape. In addition, the transparent tape was fixed on a horizontal test bench in advance. Then, one end of the separator was stretched vertically upward at a tensile speed of 50 mm / min, and the stress during peeling was measured. A total of three stress measurements were performed. The average value of the total three stresses obtained was calculated as the peel strength (N / m), and the adhesion (dry adhesion) between the electrode and the separator via the functional layer was evaluated according to the following criteria. The greater the peel strength, the better the dry adhesion.
[0270] A: Peel strength is 5.0N / m or more B: Peel strength is 3.0 N / m or more and less than 5.0 N / m C: Peel strength is 1.0 N / m or more and less than 3.0 N / m D: Peel strength less than 1.0N / m <Anti-blocking properties of functional layer> The spacer with a functional layer made in the embodiment and the comparative example (having a functional layer on both sides) is cut into two pieces of a size of 4 cm in width × 4 cm in length as a test piece. After the two test pieces obtained are overlapped in a manner that one side of the functional layer is opposite, they are pressed for 2 minutes at a temperature of 40°C and a load of 8kN to obtain a pressed body. One end of the obtained pressed body is fixed, and the other end of the pressed body is stretched vertically upward at a tensile speed of 50 mm / min, and the stress during peeling is measured, and the obtained stress is used as the adhesion strength. Then, the adhesion strength is evaluated according to the following benchmark. The smaller the adhesion strength, the better the functional layer suppresses the occurrence of adhesion, that is, the higher the adhesion resistance of the functional layer.
[0271] A: Adhesion strength is less than 4N / m B: Adhesion strength is 4N / m or more and less than 6N / m C: Adhesion strength is 6N / m or more and less than 8N / m D: Adhesion strength is 8N / m or more <Cycle characteristics of secondary batteries> After the lithium-ion secondary batteries prepared in the examples and comparative examples were injected with electrolyte, they were left to stand at a temperature of 25°C for 5 hours. Next, they were charged at a temperature of 25°C and 0.2C with a constant current method until the battery cell voltage reached 3.65V, and then aged at a temperature of 60°C for 12 hours. Then, they were discharged at a temperature of 25°C and 0.2C with a constant current method until the battery cell voltage reached 3.00V. Thereafter, CC-CV charging was performed at a constant current method of 0.2C (upper limit battery cell voltage 4.20V), and CC discharge was performed at a constant current method of 0.2C to 3.00V. The charge and discharge at 0.2C was repeated three times.
[0272] Thereafter, 200 cycles of charge and discharge were performed at a cell voltage of 4.20-3.00 V and a charge and discharge rate of 1.0 C at a temperature of 25° C. At this time, the discharge capacity of the first cycle was defined as X1, and the discharge capacity of the 200th cycle was defined as X2.
[0273] Then, the capacity retention rate ΔC′=(X2 / X1)×100(%) was calculated using the discharge capacity X1 and the discharge capacity X2, and the evaluation was performed according to the following criteria: The larger the value of the capacity retention rate ΔC′, the better the cycle characteristics of the secondary battery.
[0274] A: Capacity retention rate ΔC' is above 93% B: Capacity retention rate ΔC' is 90% or more and less than 93% C: Capacity retention rate ΔC' is 87% or more and less than 90% D: Capacity retention rate ΔC' is less than 87% (Example 1) <Preparation of granular polymer (A)> [Preparation of Monomer Composition (A)] 81.5 parts of styrene as an aromatic monovinyl monomer, 18 parts of 2-ethylhexyl acrylate as a (meth)acrylate monomer, and 0.5 parts of ethylene glycol dimethacrylate as a crosslinking monomer were mixed to prepare a monomer composition (A).
[0275] [Preparation of Metal Hydroxide] An aqueous solution (A2) obtained by dissolving 7.0 parts of sodium hydroxide in 50 parts of ion-exchanged water was gradually added to an aqueous solution (A1) obtained by dissolving 10.0 parts of magnesium chloride in 200 parts of ion-exchanged water under stirring to prepare a colloidal dispersion (A) containing magnesium hydroxide as a metal hydroxide.
[0276] [Suspension polymerization method] The granular polymer (A) is prepared by suspension polymerization. Specifically, the monomer composition (A) obtained as described above is added to the colloidal dispersion (A) containing magnesium hydroxide, and after further stirring, 3.0 parts of tert-butyl peroxy-2-ethylhexanoate (manufactured by NOF Corporation, "PERBUTYL O") as a polymerization initiator are added to obtain a mixed solution. A pipeline emulsifying disperser (manufactured by Pacific Machinery Co., Ltd., "CAVITRON") is used to perform high shear stirring on the obtained mixed solution at a rotation speed of 12000 rpm for 1 minute to form droplets of the monomer composition (A) in the colloidal dispersion containing magnesium hydroxide.
[0277] The colloidal dispersion containing magnesium hydroxide and having droplets of the monomer composition (A) formed therein was placed in a reactor and heated to 90° C. to carry out a polymerization reaction for 5 hours. The obtained dispersion was purified by decompression treatment at 90° C. for 2 hours using an evaporator to obtain an aqueous dispersion containing a particulate polymer (A).
[0278] The volume particle diameter D50 and particle size distribution α of the particulate polymer (A) were measured using the aqueous dispersion containing the particulate polymer (A).
[0279] Furthermore, while stirring the aqueous dispersion containing the granular polymer (A), sulfuric acid was added dropwise at room temperature (25°C) to perform acid washing until the pH became 6.5 or less. Next, filtration separation was performed, 500 parts of ion exchange water was added to the obtained solid component, and it was slurried again, and the water washing treatment (washing, filtration and dehydration) was repeated 10 times. After that, filtration separation was performed, and the obtained solid component was placed in a container of a dryer and dried at 40°C for 48 hours to obtain a dried granular polymer (A).
[0280] The glass transition temperature, average circularity and circularity distribution of the obtained particulate polymer (A) were measured.
[0281] <Preparation of Aqueous Dispersion Containing Binder (α)> 70 parts of ion exchange water, 0.15 parts of sodium lauryl sulfate (manufactured by Kao Chemical Co., Ltd., "EMAL (registered trademark) 2F") as an emulsifier, and 0.5 parts of ammonium persulfate as a polymerization initiator were supplied to a reactor equipped with a stirrer, the gas phase was replaced with nitrogen, and the temperature was raised to 60°C.
[0282] On the other hand, in another container, 50 parts of ion exchange water, 0.5 parts of sodium dodecylbenzenesulfonate as a dispersion stabilizer, 94 parts of n-butyl acrylate as a (meth)acrylate monomer, 2 parts of methacrylic acid as an acid group-containing monomer, 2 parts of acrylonitrile as a nitrile group-containing monomer, and 1 part of allyl methacrylate and 1 part of allyl glycidyl ether as crosslinking monomers were mixed to prepare a monomer composition (α).
[0283] The obtained monomer composition (α) was continuously added to the above-mentioned reactor with a stirrer for 4 hours to carry out polymerization. During the addition process, the reaction was carried out at 60°C. After the addition was completed, the reaction was terminated by further stirring at 70°C for 3 hours to obtain an aqueous dispersion of a granular binder (α) as an acrylic polymer. The volume particle size D50 of the obtained granular binder (α) was 0.4 μm, and the glass transition temperature was -40°C.
[0284] <Preparation of Slurry Composition (Composition for Functional Layer)> 0.5 parts of polyacrylic acid as a dispersant were added to 100 parts of alumina as heat-resistant particles (manufactured by Sumitomo Chemical Co., Ltd., "AKP3000", volume particle size D50: 0.7 μm), ion exchange water was added in such a way that the solid content concentration became 55%, and the mixture was mixed using a ball mill. Furthermore, 6 parts of an aqueous dispersion containing a binder (α) in terms of solid content were added to obtain a pre-mixing slurry.
[0285] Relative to 100 parts of the granular polymer, 0.2 parts of sodium dodecylbenzenesulfonate (Kao Chemical Co., Ltd., "Neopelex G-15") as an emulsifier and 1.5 parts of carboxymethyl cellulose as a thickener are mixed in a manner such that the solid content concentration is 40%, and then 0.5 parts of 1,2-benzo-4-isothiazoline-3-one as an amine compound are further added, and the resulting mixed solution is added to the pre-mixed slurry obtained as described above. Ion exchange water is further added in a manner such that the solid content concentration is 40% to obtain a slurry composition (composition for a functional layer). At this time, the volume ratio of the granular polymer (A) to the heat-resistant particles in the slurry composition (volume of the granular polymer (A) / volume of the heat-resistant particles) is 30 / 70. In addition, the mass ratio of the granular polymer (A) to the heat-resistant particles in the slurry composition [mass of the granular polymer (A) / mass of the heat-resistant particles] is 30 / 280.
[0286] Furthermore, the obtained slurry composition was used to measure the content of the polymerization initiator decomposition product in the particles and the amount of the particulate polymer dissolved in THF.
[0287] <Production of Separator (Laminate) with Functional Layer> A polyethylene microporous film (thickness: 12 μm) was prepared as a spacer substrate. The slurry composition obtained as described above was applied to one surface of the spacer substrate by a rod coating method. Next, the spacer substrate coated with the slurry composition was dried at 50° C. for 1 minute to form a functional layer. The same operation was performed on the other side of the spacer substrate to prepare a spacer (laminate) with a functional layer having a functional layer with a thickness of 2.0 μm on both sides of the spacer substrate.
[0288] <Production of positive electrode> 100 parts of LiCoO2 (volume average particle size: 12 μm) as a positive electrode active material, 2 parts of acetylene black (made by Denka Co., Ltd., "HS-100") as a conductive material, 2 parts of polyvinylidene fluoride (made by Kureha Co., Ltd., "#7208") as a binder for a positive electrode composite material layer, and N-methylpyrrolidone as a solvent were mixed to a total solid content concentration of 70%. They were mixed by a planetary mixer to prepare a slurry composition for a positive electrode.
[0289] The above-mentioned positive electrode slurry composition is applied to an aluminum foil with a thickness of 20 μm as a current collector and dried using a notch wheel coater in such a way that the film thickness after drying becomes about 150 μm. The drying is carried out by transporting the aluminum foil in an oven at 60 ° C for 2 minutes at a speed of 0.5 m / min. Then, the positive electrode raw material before pressing is obtained by heat treatment at 120 ° C for 2 minutes. The positive electrode raw material before pressing is rolled with a roller press to obtain a pressed positive electrode having a positive electrode composite material layer (thickness: 60 μm).
[0290] <Production of negative electrode> Add 33 parts of 1,3-butadiene, 3.5 parts of itaconic acid, 63.5 parts of styrene, 0.4 parts of sodium dodecylbenzene sulfonate as an emulsifier, 150 parts of ion exchange water, and 0.5 parts of potassium persulfate as a polymerization initiator to a 5MPa pressure-resistant container with a stirrer, stir thoroughly, heat to 50°C, and initiate polymerization. Cool at the moment when the polymerization conversion rate reaches 96%, terminate the reaction, and obtain a mixture containing a binder material (SBR) for the negative electrode composite material layer. Add 5% sodium hydroxide aqueous solution to the mixture containing the binder material for the negative electrode composite material layer, adjust the pH to 8, and remove the unreacted monomers by heating and reduced pressure distillation. Then, cool to below 30°C to obtain an aqueous dispersion containing the desired binder material for the negative electrode composite material layer.
[0291] 80 parts of artificial graphite (volume average particle size: 15.6 μm) as negative electrode active material (1) and 16 parts of silicon-based active material SiOx (volume average particle size: 4.9 μm) as negative electrode active material (2) were mixed with 2.5 parts of a 2% aqueous solution of carboxymethyl cellulose sodium salt (manufactured by Nippon Paper Industries, Ltd., “MAC350HC”) as a viscosity modifier and ion exchange water, and the solid content concentration was adjusted to 68%, and then further mixed at 25° C. for 60 minutes. Furthermore, the solid content concentration was adjusted to 62% with ion exchange water, and then further mixed at 25° C. for 15 minutes to obtain a mixed solution. To the mixed solution, 1.5 parts of the above-mentioned aqueous dispersion containing a binder for a negative electrode composite material layer and ion exchange water were added, and the final solid content concentration was adjusted to 52%, and then further mixed for 10 minutes to obtain a mixed solution. The mixed solution was degassed under reduced pressure to obtain a negative electrode slurry composition having good fluidity.
[0292] The above-mentioned negative electrode slurry composition is applied to a copper foil with a thickness of 20 μm as a current collector and dried using a notch wheel coater in such a way that the film thickness after drying becomes about 150 μm. The drying is carried out by transporting the copper foil in an oven at 60 ° C for 2 minutes at a speed of 0.5 m / min. Then, heat treatment is performed at 120 ° C for 2 minutes to obtain the negative electrode raw material before pressing. The negative electrode raw material before pressing is rolled with a roller press to obtain a pressed negative electrode having a negative electrode composite material layer (thickness: 80 μm).
[0293] The separator with a functional layer, the positive electrode, and the negative electrode obtained as described above were used to evaluate wet adhesion, dry adhesion, and blocking resistance of the functional layer.
[0294] <Manufacturing of lithium-ion secondary batteries> The pressed positive electrode prepared as described above is cut into a rectangle of 49cm×5cm, and is placed in a manner that the surface on the positive electrode composite material layer side is on the upper side, and the above-mentioned separator with a functional layer cut into 120cm×5.5cm is arranged on the positive electrode composite material layer in a manner that the positive electrode is located on one side of the length direction of the separator with a functional layer. Furthermore, the pressed negative electrode prepared as described above is cut into a rectangle of 50cm×5.2cm, and is arranged on the separator with a functional layer in a manner that the surface on the negative electrode composite material layer side is opposite to the separator with a functional layer and the negative electrode is located on the other side of the length direction of the separator with a functional layer. Then, the obtained component is wound by a winding body to obtain a winding body. The winding body is pressed at 70°C and 1MPa to form a flat body, and then packaged with an aluminum packaging material outer packaging as the outer packaging of the battery, and the electrolyte is injected in a manner that no air remains [Solvent: ethylene carbonate / diethyl carbonate / vinyl carbonate (volume ratio) = 68.5 / 30 / 1.5, electrolyte: LiPF6 with a concentration of 1M)]. Then, the opening of the outer package of the aluminum packaging material was heat-sealed at a temperature of 150° C. to produce a wound-type lithium ion secondary battery with a capacity of 800 mAh.
[0295] The obtained lithium ion secondary battery was used to evaluate the cycle characteristics of the secondary battery. The results are shown in Table 1.
[0296] (Example 2) The various operations, measurements, and evaluations were performed in the same manner as in Example 1 except that the particulate polymer (B) prepared as described below was used instead of the particulate polymer (A) when preparing the slurry composition.
[0297] <Preparation of granular polymer (B)> A granular polymer (B) was prepared in the same manner as in Example 1 except that the colloid dispersion (B) containing magnesium hydroxide was used instead of the colloid dispersion (A) containing magnesium hydroxide as the metal hydroxide when preparing the granular polymer.
[0298] The colloidal dispersion (B) containing magnesium hydroxide was prepared by slowly adding an aqueous solution (B2) obtained by dissolving 8.4 parts of sodium hydroxide in 50 parts of ion-exchanged water to an aqueous solution (B1) obtained by dissolving 12.0 parts of magnesium chloride in 200 parts of ion-exchanged water under stirring.
[0299] (Example 3) The various operations, measurements, and evaluations were performed in the same manner as in Example 1 except that the particulate polymer (C) prepared as described below was used instead of the particulate polymer (A) when preparing the slurry composition.
[0300] <Preparation of granular polymer (C)> A granular polymer (C) was prepared in the same manner as in Example 1 except that the colloid dispersion (C) containing magnesium hydroxide was used instead of the colloid dispersion (A) containing magnesium hydroxide as the metal hydroxide when preparing the granular polymer.
[0301] The colloidal dispersion (C) containing magnesium hydroxide was prepared by slowly adding an aqueous solution (C2) obtained by dissolving 5.6 parts of sodium hydroxide in 50 parts of ion-exchanged water to an aqueous solution (C1) obtained by dissolving 8.0 parts of magnesium chloride in 200 parts of ion-exchanged water under stirring.
[0302] (Example 4) The various operations, measurements, and evaluations were performed in the same manner as in Example 1 except that the particulate polymer (D) prepared as described below was used instead of the particulate polymer (A) when preparing the slurry composition.
[0303] <Preparation of granular polymer (D)> A granular polymer (D) was prepared in the same manner as in Example 1 except that the rotation speed of the disperser was changed from 12000 rpm to 13500 rpm when preparing the granular polymer.
[0304] (Example 5) The various operations, measurements, and evaluations were performed in the same manner as in Example 1 except that the particulate polymer (E) prepared as described below was used instead of the particulate polymer (A) when preparing the slurry composition.
[0305] <Preparation of granular polymer (E)> A granular polymer (E) was prepared in the same manner as in Example 1 except that the rotation speed of the disperser was changed from 12000 rpm to 10000 rpm when preparing the granular polymer.
[0306] (Example 6) The various operations, measurements, and evaluations were performed in the same manner as in Example 1 except that a particulate polymer (F) prepared as follows by an emulsion polymerization coagulation method was used instead of the particulate polymer (A) when preparing the slurry composition.
[0307] <Preparation of granular polymer (F)> (1) Preparation of resin particles 81.5 parts of styrene as an aromatic monovinyl monomer, 18 parts of 2-ethylhexyl acrylate as a (meth)acrylate monomer, and 0.5 parts of ethylene glycol dimethacrylate as a crosslinking monomer were mixed in a flask to prepare a monomer composition (F).
[0308] On the other hand, 0.7 parts of sodium dodecylbenzenesulfonate as an anionic surfactant was dissolved in 373 parts of ion-exchanged water in a separable flask to prepare a surfactant solution.
[0309] The monomer composition (F) obtained as described above was added to the surfactant solution, and dispersed using an emulsifying disperser ("Clearmix" manufactured by M Technique Co., Ltd.) to prepare an emulsified dispersion of the monomer composition (F).
[0310] After adding 400 parts of ion-exchanged water to the obtained emulsified dispersion, an aqueous solution containing 2.1 parts of potassium persulfate as a polymerization initiator (an aqueous solution prepared by dissolving 2.1 parts of potassium persulfate in 39.6 parts of ion-exchanged water) and 1.9 parts of n-octyl mercaptan as a molecular weight regulator were added, and polymerization was carried out at 80° C. for 3 hours (first stage polymerization).
[0311] Furthermore, after adding an aqueous solution containing 3.2 parts of potassium persulfate as a polymerization initiator (an aqueous solution prepared by dissolving 3.2 parts of potassium persulfate in 61.3 parts of ion-exchanged water), 81.1 parts of styrene as an aromatic monovinyl monomer, 12.0 parts of methacrylic acid and 36.8 parts of n-butyl acrylate as (meth)acrylate monomer units, and 2.1 parts of n-octyl mercaptan as a molecular weight modifier were added dropwise. After the dropwise addition, polymerization was performed by maintaining the original temperature (80° C.) for 2 hours (second stage polymerization).
[0312] After the polymerization, the reaction solution was cooled with water to obtain a dispersion solution containing resin fine particles.
[0313] (2) Preparation of resin particles 150 parts of the dispersion containing resin particles obtained as described above and 645 parts of ion exchange water were added to a flask and stirred. The temperature of the obtained dispersion was adjusted to 30°C, and then sodium hydroxide aqueous solution (concentration: 5 mol / L) was added until the pH was 10.
[0314] Next, an aqueous solution prepared by dissolving 32 parts of magnesium chloride hexahydrate in 32 parts of ion-exchanged water was added to the above dispersion under stirring at 30° C. for 10 minutes. Thereafter, the dispersion was heated to 90° C. over 60 minutes, and while stirring and heating were continued, aggregation due to salting out of the resin fine particles and fusion due to heating were performed to form resin particles.
[0315] Then, while continuing to stir and heat, the particle size of the resin particles was measured using a particle size measuring machine (manufactured by Beckman Coulter, "Multisizer"). When the volume particle size D50 of the formed resin particles reached 3 μm, an aqueous solution prepared by dissolving 8.8 parts of sodium chloride in 57.7 parts of ion exchange water was added to stop salting out and welding. Heating and stirring were continued at 90° C. for 3 hours to control the particle shape, thereby obtaining a dispersion containing a particulate polymer (F1).
[0316] In addition, the particle size of the resin particles was measured using a particle size measuring machine while continuing stirring and heating in the same procedure. When the volume particle size D50 of the formed resin particles reached 5 μm, an aqueous solution prepared by dissolving 8.8 parts of sodium chloride in 57.7 parts of ion exchange water was added to stop salting out and welding. Heating and stirring were continued at 90° C. for 3 hours to control the particle shape, thereby obtaining a dispersion containing a particulate polymer (F2).
[0317] The dispersion containing the particulate polymers (F1) and (F2) obtained above is added in appropriate amounts to obtain a dispersion containing the particulate polymer (F) having a target volume particle size D50 and a particle size distribution α.
[0318] The dispersion containing the particulate polymer (F) was dehydrated, washed 10 times with ion-exchanged water, and then dried in a vacuum dryer at a pressure of 30 Torr and a temperature of 50° C. for 1 day to obtain a particulate polymer (F).
[0319] (Example 7) The results are shown in Table 1, except that the particulate polymer (G) prepared as follows was used instead of the particulate polymer (A) when preparing the slurry composition.
[0320] <Preparation of granular polymer (G)> When preparing the granular polymer, a granular polymer (G) was prepared by the same operation as in Example 1 except that styrene as the aromatic monovinyl monomer was changed from 81.5 parts to 81.8 parts and ethylene glycol dimethacrylate as the crosslinking monomer was changed from 0.5 parts to 0.2 parts.
[0321] (Example 8) The various operations, measurements, and evaluations were performed in the same manner as in Example 1 except that the particulate polymer (H) prepared as described below was used instead of the particulate polymer (A) when preparing the slurry composition.
[0322] <Preparation of granular polymer (H)> When preparing the granular polymer, a granular polymer (H) was prepared by the same operation as in Example 1 except that styrene as the aromatic monovinyl monomer was changed from 81.5 parts to 77 parts and ethylene glycol dimethacrylate as the crosslinking monomer was changed from 0.5 parts to 5 parts.
[0323] (Example 9) The various operations, measurements, and evaluations were performed in the same manner as in Example 1 except that the particulate polymer (I) prepared as described below was used instead of the particulate polymer (A) when preparing the slurry composition.
[0324] <Preparation of granular polymer (I)> A granular polymer (I) was prepared by the same operation as in Example 1 except that 0.5 parts of ethylene glycol dimethacrylate as a crosslinking monomer was changed to 0.5 parts of divinylbenzene when preparing the granular polymer.
[0325] (Example 10) The various operations, measurements, and evaluations were performed in the same manner as in Example 1 except that the particulate polymer (J) prepared as described below was used instead of the particulate polymer (A) when preparing the slurry composition.
[0326] <Preparation of granular polymer (J)> When preparing the granular polymer, the same operation as in Example 1 was carried out except that styrene as the aromatic monovinyl monomer was changed from 81.5 parts to 81.9 parts, and 0.5 parts of ethylene glycol dimethacrylate as the crosslinking monomer was changed to 0.1 parts of trimethylolpropane trimethacrylate to prepare a granular polymer (J).
[0327] (Example 11) The various operations, measurements, and evaluations were performed in the same manner as in Example 1 except that the particulate polymer (K) prepared as described below was used instead of the particulate polymer (A) when preparing the slurry composition.
[0328] <Preparation of granular polymer (K)> When preparing the granular polymer, the same operation as in Example 1 was carried out except that styrene as the aromatic monovinyl monomer was changed from 81.5 parts to 76.8 parts, 0.5 parts of ethylene glycol dimethacrylate as the crosslinking monomer was changed to 5 parts of glycidyl methacrylate, and 0.2 parts of methacrylic acid as the acid group-containing monomer was further added to prepare a granular polymer (K).
[0329] (Example 12) The various operations, measurements, and evaluations were performed in the same manner as in Example 1 except that the particulate polymer (L) prepared as described below was used instead of the particulate polymer (A) when preparing the slurry composition.
[0330] <Preparation of granular polymer (L)> A particulate polymer (L) was prepared by carrying out the same operation as in Example 1 except that the reduced pressure treatment time using the evaporator was changed to 1 hour when preparing the particulate polymer.
[0331] (Example 13) The various operations, measurements, and evaluations were performed in the same manner as in Example 1 except that the particulate polymer (M) prepared as described below was used instead of the particulate polymer (A) when preparing the slurry composition.
[0332] <Preparation of granular polymer (M)> A granular polymer (M) was prepared by carrying out the same operation as in Example 1 except that the reduced pressure treatment time using the evaporator was changed to 0.5 hours when preparing the granular polymer.
[0333] (Example 14) The various operations, measurements, and evaluations were performed in the same manner as in Example 1, except that the aqueous dispersion containing the binder (β) prepared as described below was used instead of the aqueous dispersion containing the binder (α) when preparing the slurry composition.
[0334] <Preparation of Aqueous Dispersion Containing Binder (β)> 70 parts of ion exchange water, 0.15 parts of polyoxyethylene lauryl ether (manufactured by Kao Chemical Co., Ltd., "EMULGEN (registered trademark) 120") as an emulsifier, and 0.5 parts of ammonium persulfate as a polymerization initiator were supplied to a reactor equipped with a stirrer, the gas phase was replaced with nitrogen, and the temperature was raised to 60°C.
[0335] On the other hand, in another container, 50 parts of ion-exchanged water, 0.5 parts of polyoxyethylene lauryl ether (manufactured by Kao Chemical Co., Ltd., "EMULGEN (registered trademark) 120") as an emulsifier, 70 parts of 2-ethylhexyl acrylate as a (meth)acrylate monomer, 25 parts of styrene as an aromatic monovinyl monomer, 1.7 parts of allyl glycidyl ether and 0.3 parts of allyl methacrylate as crosslinking monomers, and 3 parts of acrylic acid as an acid group-containing monomer were mixed to prepare a monomer composition (β).
[0336] The obtained monomer composition (β) was continuously added to the above-mentioned reactor with a stirrer for 4 hours to carry out polymerization. During the addition process, the reaction was carried out at 70°C. After the addition was completed, the reaction was terminated after further stirring at 80°C for 3 hours to obtain an aqueous dispersion containing a granular binder (β). The volume particle size D50 and glass transition temperature of the binder (β) were measured using the obtained aqueous dispersion containing the binder (β). The volume particle size D50 of the binder (β) was 0.25 μm, and the glass transition temperature was -35°C.
[0337] (Example 15) When preparing the slurry composition, various operations, measurements, and evaluations were performed in the same manner as in Example 1, except that 100 parts of alumina as the heat-resistant particles was replaced with 100 parts of boehmite (manufactured by Showa Denko K.K., "H43M", volume particle size D50: 0.8 μm). The results are shown in Table 1.
[0338] (Example 16) When preparing the slurry composition, various operations, measurements and evaluations were performed in the same manner as in Example 1, except that 100 parts of alumina as the heat-resistant particles were replaced with 100 parts of magnesium hydroxide (MAGSEEDS X-6F manufactured by Kojima Chemical Co., Ltd., volume particle size D50: 0.7 μm). The results are shown in Table 1.
[0339] (Example 17) When preparing the slurry composition, various operations, measurements, and evaluations were performed in the same manner as in Example 1, except that 100 parts of alumina as the heat-resistant particles were replaced with 100 parts of barium sulfate (TS-2 manufactured by Takehara Chemical Co., Ltd., volume particle size D50: 0.3 μm). The results are shown in Table 1.
[0340] (Example 18) The various operations, measurements, and evaluations were performed in the same manner as in Example 1 except that 0.5 parts of 1,2-benzo-4-isothiazoline-3-one as the amine compound was changed to 0.5 parts of 2-methyl-4-isothiazoline-3-one when preparing the slurry composition.
[0341] (Example 19) The various operations, measurements, and evaluations were performed in the same manner as in Example 1, except that the aqueous dispersion containing the binder (γ) prepared as described below was used instead of the aqueous dispersion containing the binder (α) when preparing the slurry composition.
[0342] <Preparation of Aqueous Dispersion Containing Binder (γ)> 150 parts of ion exchange water, 25 parts of sodium dodecylbenzenesulfonate aqueous solution (concentration 10%) as an emulsifier, 63 parts of styrene as an aromatic monovinyl monomer, 3.5 parts of itaconic acid as a monomer having a carboxylic acid group, 1 part of 2-hydroxyethyl acrylate as a monomer having a hydroxyl group, and 0.5 parts of tert-dodecyl mercaptan as a molecular weight regulator were sequentially added to the reactor. Next, after replacing the gas inside the reactor with nitrogen three times, 32.5 parts of 1,3-butadiene as a conjugated diene monomer were added. 0.5 parts of potassium persulfate as a polymerization initiator were added to the reactor maintained at 60°C to initiate the polymerization reaction, and the polymerization reaction was continued while stirring. At the moment when the polymerization conversion rate reached 96%, 0.1 parts of hydroquinone aqueous solution (concentration 10%) as a polymerization terminator was added to terminate the polymerization reaction. Then, the residual monomers were removed using a rotary evaporator at a water temperature of 60°C to obtain an aqueous dispersion of polymer B (granular polymer). The volume particle size D50 and glass transition temperature of the binder (γ) were measured using the obtained aqueous dispersion containing the binder (γ). The volume particle size D50 of the binder (γ) was 0.15 μm, and the glass transition temperature was 15°C.
[0343] (Comparative Example 1) The various operations, measurements, and evaluations were performed in the same manner as in Example 1 except that the particulate polymer (N) prepared as described below was used instead of the particulate polymer (A) when preparing the slurry composition.
[0344] <Preparation of granular polymer (N)> A granular polymer (N) was prepared in the same manner as in Example 1 except that the rotation speed of the disperser was changed from 12000 rpm to 15000 rpm when preparing the granular polymer.
[0345] (Comparative Example 2) The various operations, measurements, and evaluations were performed in the same manner as in Example 1 except that the particulate polymer (O) prepared as described below was used instead of the particulate polymer (A) when preparing the slurry composition.
[0346] <Preparation of granular polymer (O)> A granular polymer (O) was prepared in the same manner as in Example 1 except that the rotation speed of the disperser was changed from 12000 rpm to 8000 rpm when preparing the granular polymer.
[0347] In addition, in Table 1, "ST" represents styrene unit, "2EHA" means 2-ethylhexyl acrylate units, "EDMA" means ethylene glycol dimethacrylate units, "BA" represents n-butyl acrylate unit, "DVB" means divinylbenzene unit, "TMP" means trimethylolpropane trimethacrylate units, "GMA" means glycidyl methacrylate units, "MAA" means methacrylic acid units, "AN" stands for acrylonitrile unit, "AMA" means allyl methacrylate units, "AGE" means allyl glycidyl ether unit, "AA" represents acrylic acid unit, "IA" represents itaconic acid unit, "2HEA" means 2-hydroxyethyl acrylate unit, "BD" represents butadiene units, "Suspension" refers to a particulate polymer obtained by suspension polymerization. "Emulsion" refers to a particulate polymer obtained by emulsion polymerization. "BIT" means 1,2-benzo-4-isothiazolin-3-one, "MIT" stands for 2-methyl-4-isothiazolin-3-one.
[0348] [Table 1]
[0349] As can be seen from Table 1, the functional layers formed using the electrochemical element functional layer compositions of Examples 1 to 19 were excellent in wet adhesiveness.
[0350] Industrial Applicability According to the present invention, there can be provided a composition for an electrochemical element functional layer capable of forming a functional layer having excellent wet adhesiveness.
[0351] Furthermore, according to the present invention, there can be provided an electrochemical device laminate having a functional layer formed using the electrochemical device functional layer composition and an electrochemical device having the electrochemical device laminate.
Claims
1. A composition for an electrochemical element functional layer, comprising a particulate polymer, The particulate polymer has a volume particle size D50 of 1.0 μm or more and 10.0 μm or less, The particulate polymer has a particle size distribution α, wherein the proportion of particles having a particle size that is 1.5 times or more of the volume particle size D50 is 0.5% by volume or more and 5.0% by volume or less when the particulate polymer is taken as 100% by volume, The particulate polymer is formed of particles containing a polymer having an aromatic monovinyl monomer unit and a crosslinking monomer unit.
2. The composition for an electrochemical element functional layer according to claim 1, wherein The particulate polymer has a volume particle size D50 of 2.3 μm or more and 9.0 μm or less, The particulate polymer has a particle size distribution α in which, when the particulate polymer is taken as 100% by volume, the proportion of particles having a particle diameter that is 1.5 times or more the volume particle diameter D50 is 1.0% by volume or more and 5.0% by volume or less.
3. The composition for an electrochemical element functional layer according to claim 1, wherein The particulate polymer has a volume particle size D50 of 2.3 μm or more and 8.2 μm or less, The particulate polymer has a particle size distribution α in which, when the particulate polymer is taken as 100% by volume, the proportion of particles having a particle diameter that is 1.5 times or more the volume particle diameter D50 is 1.2% by volume or more and 4.7% by volume or less.
4. The composition for an electrochemical element functional layer according to claim 1, wherein The polymer also contains (meth)acrylate monomer units, The (meth)acrylic acid ester monomer forming the (meth)acrylic acid ester monomer unit is at least one of an alkyl acrylate and an alkyl methacrylate.
5. The composition for an electrochemical element functional layer according to claim 4, wherein The (meth)acrylate monomer is at least one of n-butyl acrylate, 2-ethylhexyl acrylate, and methyl methacrylate.
6. The composition for an electrochemical element functional layer according to claim 5, wherein The (meth)acrylate monomer is at least one of n-butyl acrylate and 2-ethylhexyl acrylate.
7. The composition for an electrochemical element functional layer according to claim 1, wherein The crosslinkable monomer unit contained in the polymer is at least one selected from the group consisting of an aromatic divinyl monomer unit, a di(meth)acrylate monomer unit, a tri(meth)acrylate monomer unit, and an ethylenically unsaturated monomer unit containing an epoxy group.
8. The composition for an electrochemical element functional layer according to claim 1, wherein The monomer forming the crosslinkable monomer unit is at least one of ethylene glycol dimethacrylate, divinylbenzene, trimethylolpropane trimethacrylate, and glycidyl methacrylate.
9. The composition for an electrochemical element functional layer according to claim 1, wherein The aromatic monovinyl monomer forming the aromatic monovinyl monomer unit is at least one of styrene, α-methylstyrene, butoxystyrene, and vinylnaphthalene.
10. The composition for an electrochemical element functional layer according to claim 9, wherein The aromatic monovinyl monomer is styrene.
11. The composition for an electrochemical element functional layer according to claim 1, wherein The particulate polymer has a volume particle size D50 of 2.3 μm or more and 8.2 μm or less, The particulate polymer has a particle size distribution α in which, when the particulate polymer is taken as 100% by volume, the proportion of particles having a particle diameter that is 1.5 times or more the volume particle diameter D50 is 1.2% by volume or more and 4.5% by volume or less.
12. The composition for an electrochemical element functional layer according to claim 1, wherein The particulate polymer has a volume particle size D50 of 2.3 μm or more and 8.2 μm or less, The particulate polymer has a particle size distribution α, wherein the proportion of particles having a particle diameter that is 1.5 times or more the volume particle diameter D50 is 1.5% by volume or more and 4.0% by volume or less when the particulate polymer is taken as 100% by volume.
13. The composition for an electrochemical element functional layer according to claim 1, wherein The particulate polymer has a volume particle size D50 of 2.3 μm or more and 8.2 μm or less, The particulate polymer has a particle size distribution α in which, when the particulate polymer is taken as 100% by volume, the proportion of particles having a particle diameter that is 1.5 times or more the volume particle diameter D50 is 1.5% by volume or more and 3.2% by volume or less.
14. The composition for an electrochemical element functional layer according to claim 1, wherein The particulate polymer has a particle size distribution α, wherein the proportion of particles having a particle diameter that is 3.0 times or more of the volume particle diameter D50 is 2.0 volume % or less when the particulate polymer is taken as 100 volume %.
15. The composition for an electrochemical element functional layer according to claim 1, wherein The particulate polymer has a particle size distribution α, wherein the proportion of particles having a particle diameter that is 3.0 times or more of the volume particle diameter D50 is 1.5% by volume or less when the particulate polymer is taken as 100% by volume.
16. The composition for an electrochemical element functional layer according to claim 1, wherein The particulate polymer has a particle size distribution α in which, when the particulate polymer is taken as 100% by volume, the proportion of particles having a particle diameter that is 3.0 times or more of the volume particle diameter D50 is 0.15% by volume or more and 1.5% by volume or less.
17. The composition for an electrochemical element functional layer according to claim 1, wherein The particulate polymer has an average circularity of 0.95 or more and 0.99 or less, The particulate polymer has a circularity distribution in which the proportion of particles having a circularity of less than 0.95 is less than 10% on a number basis relative to the particulate polymer.
18. The composition for an electrochemical element functional layer according to claim 1, wherein The amount of the particulate polymer dissolved in tetrahydrofuran is 5 mass % or more and 50 mass % or less.
19. The composition for an electrochemical element functional layer according to claim 1, wherein The content ratio of the polymerization initiator decomposition products in the particles constituting the particulate polymer is 20 ppm or less relative to the total mass of the particles constituting the particulate polymer.
20. The composition for an electrochemical element functional layer according to claim 1, wherein The composition for an electrochemical element functional layer further comprises a binder.
21. The composition for an electrochemical element functional layer according to claim 20, wherein The bonding material contains a (meth)acrylate monomer unit and an acid group-containing monomer unit.
22. The composition for an electrochemical element functional layer according to claim 1, wherein The electrochemical element functional layer composition further includes an amine compound.
23. The composition for an electrochemical element functional layer according to any one of claims 1 to 22, wherein The electrochemical element functional layer composition further includes non-conductive heat-resistant particles.
24. A laminate for an electrochemical element, comprising a substrate and a functional layer formed on the substrate, The functional layer is formed using the composition for an electrochemical element functional layer according to any one of claims 1 to 23. 25 . An electrochemical element comprising the laminate for an electrochemical element according to claim 24 .
Citation Information
Patent Citations
Electrode for secondary battery, binder for secondary battery electrode, manufacturing method and secondary battery
JP2012204303A
Slurry composition for secondary battery porous film, secondary battery electrode, secondary battery separator, and secondary battery
JP2013145763A
Composition for electrochemical element functional layer, functional layer for electrochemical element, and electrochemical element
WO2020175292A1